Updates to the RIFM Criteria Document for fragrance ingredient evaluation - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Temperature, taphonomy, or technique? Contrasting hypotheses of ancient DNA recovery from Quaternary asphaltic fossil deposits - Robin R. Singleton; Kristen M. Rayfield; Karissa S. Hughes; Ezra M. Flint; Karin A. Rice; Laura R. Tewksbury; Sean C. Campbell; Aisling B. Farrell; John R. Southon; Emily L. Lindsey; Courtney A. Hofman; Alexis M. Mychajliw (Quaternary Science Reviews, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-propanol, 1,1′,1′,1'-(1,2-ethanediyldinitrilo)tetrakis-, CAS Registry Number 102-60-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, octyl crotonate, CAS Registry Number 22874-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, propenylguaethol, CAS Registry Number 94-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxybutyrate, CAS Registry Number 5405-41-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(p-tert-butylphenyl)-2-methylpropanol, CAS Registry Number 56107-04-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxyhexanoate, CAS Registry Number 2305-25-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, linoleic acid, CAS Registry Number 60-33-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-naphthyl isobutyl ether, CAS Registry Number 2173-57-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,5-dimethylhexyl acetate, CAS Registry Number 67952-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(4-methyl-3-pentenyl)-3-cyclohexene-1-carbonitrile, CAS Registry Number 68084-04-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexaneethyl acetate, CAS Registry Number 21722-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3,5,5-trimethylcyclohexanol, CAS Registry Number 116-02-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 5-methyl-2-phenyl-2-hexenal, CAS Registry Number 21834-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-heptanol, 2,6-dimethyl-,acetate, CAS Registry Number 10250-45-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, phenylacetaldehyde glyceryl acetal, CAS Registry Number 29895-73-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanemethanol, 2,4-dimethyl-, CAS Registry Number 68480-15-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2,2,6-trimethylcyclohexanone, CAS Registry Number 2408-37-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cis-4-(isopropyl)cyclohexanemethanol, CAS registry number 13828-37-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanone, 2-ethyl-4,4-dimethyl-, CAS registry number 55739-89-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, squalene, CAS Registry Number 111-02-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-guaiene, CAS Registry Number 88-84-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3-hexene, 1,1′,''-[ethylidynestris(oxy)]tris-, (3Z, 3′Z,3"Z)-, CAS registry number 215305-10-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hydroxyhexanoate, CAS Registry Number 21188-58-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-2-phenyl-2-pentenal, CAS Registry Number 26643-91-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-phenyl-2-butenal, CAS Registry Number 4411-89-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dodecyldimethylamine oxide, CAS Registry Number 1643-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tricosane, CAS Registry Number 638-67-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 2-nonenoate, CAS registry number 111-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-(isopropyl)-β-methylcyclohexanethanol, CAS Registry Number 67634-03-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Photosynthetic responses of Trinitario cacao genotypes under four light levels - Vernessa R. Lewis; Aidan D. Farrell; Pathmanathan Umaharan; Adrian M. Lennon (Trees, 2026)

RIFM fragrance ingredient safety assessment, undecanol, CAS Registry Number 30207-98-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl cis-5-octenoate, CAS Registry Number 41654-15-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-nonenoate, CAS Registry Number 13481-87-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methyl-3-penten-2-one, CAS Registry Number 141-79-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hexenoate, CAS Registry Number 2396-78-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Corrigendum to “Temperature, taphonomy, or technique? Contrasting hypotheses of ancient DNA recovery from Quaternary asphaltic fossil deposits” [Quat. Sci. Rev. 389 (2026) 110106] - Robin Singleton; Kristen M. Rayfield; Karissa S. Hughes; Ezra M. Flint; Karin A. Rice; Laura R. Tewksbury; Sean C. Campbell; Aisling B. Farrell; John R. Southon; Emily L. Lindsey; Courtney A. Hofman; Alexis M. Mychajliw (Quaternary Science Reviews, 2026)

Identifying a new candidate space crop: the alpine strawberry Fragaria vesca - K. Nakashima; C. Farrell; J. Calabria; A. H. Millar; G. Massa; M. Watt (Life Sciences in Space Research, 2026)

Extreme environmental conditions and land use drive phytoplankton turnover and homogenization across a climatic gradient - Irina Izaguirre; M. Laura Sánchez; M. Romina Schiaffino; Inés O’Farrell; Gerardo Cueto; Paula Huber; Miguel Mancini; Fabián Grosman; Josefina Zunino (Hydrobiologia, 2026)

Floodplain-lake hydroperiod modulates the response of zooplankton and phytoplankton resting stages to extreme droughts - G. Chaparro; I. O’Farrell; N. S. Morandeira; M. P. Gayol (Hydrobiologia, 2026)

Leveraging Pharmacy Education through a Train-the-Trainer Model to Enhance Breast Cancer Literacy in Rural Communities - Christopher L. Farrell; Melanie R. Ginzburg; Morgan B. Enlow; Missouri M. Jenkins; Alexus N. Hames; Cayla R. Adams; Marlana A. Roberts; Hillary E. Stamps; Natalie A. Paxton; Courtney N. Addison; Austin Y. Shull (Journal of Cancer Education, 2026)
Rural versus urban communities experience disproportionate challenges in breast cancer outcomes, with higher breast cancer mortality and later stage disease presentation, despite similar diagnosis rates. These disparities are driven by structural barriers, including rural hospital closures, transportation difficulties, and limited access to oncology specialists. This study evaluated a train-the-trainer program designed to equip PharmD students located at a pharmacy school in a rural county in South Carolina with breast cancer education training, leveraging the pharmacists’ position as accessible healthcare professionals in rural communities. Training focused on breast cancer risk factors, prevention, screening, genetics, staging, and treatment options. Effectiveness was measured through pre- and post-workshop confidence surveys and knowledge assessments. Results showed significant improvement in student confidence across educational domains, with average scores increasing from 6.30 to 8.59 ( p < 0.0001). Understanding of screening guidelines (mean difference: 4.30; p -value: < .0001) and target therapy options showed the greatest improvement (mean difference: 3.65; p -value: < .0001), while knowledge of BRCA gene inheritance showed the smallest change (mean difference: 0.369; p -value: ns), suggesting some pre-existing awareness but limited understanding of its clinical applications. Overall, this pilot program demonstrates how pharmacy education can address healthcare disparities in rural communities. By preparing pharmacists to deliver accurate breast cancer education and to increase rural patient agency, this model creates a sustainable approach to improving health literacy in medically underserved areas. Future research could further expand this model to include diverse healthcare professionals and incorporate long-term impact assessments in community settings.

The immunogenic potential of AZD1402 (Elarekibep) T-cell epitopes in healthy volunteers and drug-exposed clinical trial participants - Liam Farrell; Stephanie M Bates; Alexander Walker; Monday Ogese; Xiaoli Meng; Sian Piper; John Mo; Katy Saide; Jorrit Hornberg; David Close; Ian Wallace; Catherine J Betts; et al. (Archives of Toxicology, 2026)
AZD1402 (Elarekibep) is a novel anticalin with engineered IL-4Rα antagonist binding properties that was under development for inhaled treatment of asthma. Structural similarity to tear-lipocalin is thought to limit immunogenicity risk; however, a range of treatment-emergent hypersensitivity-like adverse events were observed in a clinical study. This study aimed to (i) explore the activation of drug-exposed human T-cells with AZD1402- and tear lipocalin-derived peptides, (ii) characterise any T-cell epitopes contained within AZD1402 and (iii) define the nature of any response. Peripheral blood mononuclear cells (PBMC) from AZD1402-exposed study participants, alongside AZD1402-naïve donors, were cultured with AZD1402 and AZD1402-derived overlapping 18mer peptides. Proliferation and cytokine secretion were measured. T-cell clones were generated to characterise the diversity of T-cell epitopes and reactivity against equivalent tear-lipocalin peptides. AZD1402 contained multiple epitopes located in engineered “hotspot” regions of the molecule that activated PBMC and MHC class II-restricted CD4 + T-cell clones from both study participants and AZD1402-naïve donors. T-cell stimulatory peptides contained amino acid substitutions generated through mutagenesis to create AZD1402 target binding properties; similar T-cell epitopes were not found in tear-lipocalin. Detection of T-cell clones responsive towards AZD1402 and AZD1402-derived peptides provides evidence that immunogenic epitopes are formed naturally through processing of the AZD1402. These data describe a recall immunogenicity risk associated with AZD1402 and provide a framework by which to explore the immunogenic potential of modified sequences within anticalin or other large molecule therapeutics.

RIFM fragrance ingredient safety assessment, 1-(1,2,3,4,5,6,7,8-octahydro-2,3,8,8-tetramethyl-2-naphthalenyl)ethanone, CAS Registry Number 54464-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, docosane, CAS Registry Number 629-97-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl jasmonate, CAS Registry Number 1211-29-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-isobutyl-4-methyltetrahydro-2H-pyran-4-ol, CAS Registry Number 63500-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dimyrcene, CAS Registry Number 532-87-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl myristate, CAS Registry Number 124-10-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2,4-bis(1-methylethenyl)-, (1R,2R,4S)-rel-, CAS Registry Number 33880-83-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl myristate, CAS Registry Number 124-06-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-methylpentyl 2-methylvalerate, CAS Registry Number 90397-38-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pyrazine, methyl (methylthio)-, CAS Registry Number 67952-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-propenoic acid, 2-[1-(3,3-dimethylcyclohexyl)ethoxy]-2-methylpropyl ester, CAS Registry Number 820975-49-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecyl palmitate, CAS Registry Number 540-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2-(1-methylethenyl)-4-(1-methylethyl)-, didehydro derivative, CAS Registry Number 68845-33-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, acetyl cedrene, CAS Registry Number 32388-55-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, butyl sulfide, CAS Registry Number 544-40-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heneicosane, CAS Registry Number 629-94-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl palmitate, CAS Registry Number 628-97-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, sclareol, CAS registry number 515-03-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl octadecanoate, CAS Registry Number 111-61-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexyl methyl pentanone, CAS Registry Number 4927-39-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heptadecane, CAS Registry Number 629-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecane, CAS Registry Number 544-76-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, oleic acid, CAS Registry Number 112-80-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pentadecane, CAS Registry Number 629-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tetradecane, CAS Registry Number 629-59-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, nonadecane, CAS Registry Number 629-92-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, octadecane, CAS Registry Number 593-45-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, eicosane, CAS Registry Number 112-95-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessments, ethyl ricinoleate, CAS Registry Number 55066-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-8-methylenetricyclo[3.3.1.(3,7)]decan-2-yl acetate, CAS Registry Number 122760-85-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Reconstructing prehistoric land cover and landuse in complex ‘blue-green’ landscapes - Kimberley L. Davies; M. Jane Bunting; Willem Koster; Nicki J. Whitehouse; Michelle Farrell; Henry Chapman; Jason R. Kirby; J. Edward Schofield; Phil Barratt; Benjamin Gearey; Nika Shilobod (Vegetation History and Archaeobotany, 2026)

Not all forest edges are the same: agricultural edges have the greatest impacts on ant-mediated seed dispersal of temperate forest myrmecochores - Catherine A. Farrell; Amber C. Churchill; Xingqiu Mei; Weixing Zhu; Kirsten M. Prior (Biodiversity and Conservation, 2026)
Contemporary temperate forest ecosystems are fragmented and set within matrices of surrounding landscapes with various land uses, generating forest-edge habitats with distinct conditions that influence forest organisms and their interactions. Seed-dispersal by ants (myrmecochory) is a prominent interaction for temperate forest understory plants. Here, we examine the effects of forest edges in common surrounding landscapes in eastern North America on myrmecochory and whether environmental variables mediate the differences between edges and interior forest patches. We measured seed dispersal by ants, the abundance of the primary seed-dispersing ant, Aphenogaster sp., the presence of myrmecochores (plants with ant-dispersed seeds), the abundance of seed antagonists, and environmental variables in forests surrounded by agriculture, residential development, or low-maintenance landscapes. We found that organisms involved in myrmecochory were generally reduced at edges compared to forest interiors. Agricultural edges were the most altered, with the greatest differences in environmental conditions and loss of myrmecochores compared to interiors. Myrmecochory in forest interiors was unaffected by surrounding landscape types, and some edge types were more conducive to myrmecochory than others. These findings suggest that preserving forest interiors is important for the persistence of myrmecochory. Additionally, restoration of myrmecochores, which are reduced in many contemporary forests, would benefit from the increased seed-dispersal capacity of forest interiors and from the conditions of some edge types.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

From kelp forests to turf reefs: Patterns, drivers, and impacts to functional diversity - Shane P. Farrell; Dara S. Yiu; Stuart K. Ryan; Rene D. Francolini; Courtney E. Stuart; Jonathan S. Lefcheck; Yasmina M. Shah Esmaeili; Douglas B. Rasher (Ecology, 2026)
Kelp forests are declining in many regions due to ocean warming, predator loss, and other anthropogenic stressors. In areas of rapid ocean warming, including the southern Gulf of Maine, these ecosystems have transitioned to a novel state dominated by low‐lying mats of turf algae. However, the pace, drivers, and ecological consequences of this transition remain unclear. Here, we used field surveys from 32 sites over 5 years (2018–2023) to reveal a continuation of kelp forest collapse and northward expansion of turf algae across Maine's coast. Next, we united data on benthic cover with key environmental variables in a structural equation model to show that turf algae were directly enhanced by higher ocean temperatures and decreased wave disturbance and indirectly enhanced by a warming‐induced loss of kelp cover. Lastly, we revealed the shift from kelp to turf yielded a seaweed assemblage dominated by traits associated with rapid growth, high surface area‐to‐volume ratios, and markedly reduced canopy height, indicating declines in habitat provisioning and carbon storage with kelp forest loss. Our findings highlight the accelerating impacts of climate change on temperate reef ecosystems and the vital services they provide. Further, we provide insights into a new state shift that is now occurring globally and underscore the need for urgent actions to mitigate further loss of foundational kelp forests.

RIFM fragrance ingredient safety assessment, phytyl acetate, CAS Registry Number 10236-16-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, [2,2-bis[(3,7-dimethyl-2,6-octadienyl)oxy]ethyl]benzene, CAS Registry Number 67634-02-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2,3,5,6-tetramethylpyrazine, CAS Registry Number 1124-11-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cedryl methyl ether, CAS Registry Number 67874-81-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl 2-(formylamino)benzoate, CAS Registry Number 41270-80-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, naphtho[2,1-b]furan, dodecahydro-3a,6,6,9a-tetramethyl-, (3aR,5aS,9aS,9bR)-, CAS Registry Number 6790-58-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, laurel leaf oil, CAS Registry Number 8007-48-5, RIFM ID 476-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, (Z)-2-penten-1-ol, CAS Registry Number 1576-95-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-3,5-heptadien-2-one, CAS Registry Number 1604-28-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopropylphenylbutanal, CAS Registry Number 125109-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl cinnamate, CAS Registry Number 103-26-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, lovage leaf oil, CAS Registry Number 8016-31-7, RIFM ID 813-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β,β,3-trimethyl benzenepropanol, CAS Registry Number 103694-68-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-β-ionone, CAS registry number 17283-81-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-hexanone, CAS Registry Number 589-38-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl methylphenylglycidate, CAS Registry Number 77-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-α-ionone, CAS Registry Number 31499-72-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, hinoki root oil, CAS Registry Number 91745-97-0, RIFM ID 5487-A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobornyl methyl ether, CAS Registry Number 5331-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl safranate, CAS registry number 35044-57-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, Bucchu oil, betulina, CAS Registry Number 68650-46-4, RIFM ID 73-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl pyruvate, CAS registry number 617-35-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, thyme oil, red, CAS Registry Number 8007-46-3, RIFM ID 471.E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-methyl-3-tolylpropionaldehyde, CAS Registry Number 41496-43-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dihydrocarvyl acetate, CAS Registry Number 20777-49-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-2,6-nonadien-1-al, CAS Registry Number 41448-29-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopulegyl acetate, CAS Registry number 57576-09-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, anisyl alcohol, CAS Registry Number 105-13-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, bicyclo[3.1.0]hexan-3-one, 4-methyl-1-(1-methylethyl)-, CAS Registry Number 1125-12-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-isopropyl-2(1H)-octahydronaphthalenone, CAS Registry Number 34131-98-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl 3-phenylglycidate, CAS Registry Number 121-39-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, citral, CAS Registry Number 5392-40-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,6-octadien-3-ol, 3,7-dimethyl-, acid-isomerized, CAS Registry Number 73018-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 1,1-dimethoxycyclododecane, CAS Registry Number 950-33-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-ethyl-5-methoxybicyclo[2.2.1]heptane, CAS registry number 122795-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, styrax absolute, CAS registry Number 8024-01-9, RIFM ID 6877.K2.1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α,α-dimethyl-p-ethylphenylpropanal, CAS Registry Number 67634-15-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α-hexylcinnamaldehyde, CAS Registry Number 101-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-octalactone, CAS Registry number 104-50-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methoxybenzoic acid, CAS Registry Number 100-09-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-methyl-2-butenyl acetate, CAS Registry Number 1191-16-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-hexalactone, CAS Registry Number 695-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, myristic acid, CAS Registry Number 544-63-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobutyric acid, CAS Registry Number 79-31-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-decalactone, CAS Registry Number 706-14-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-undecalactone, CAS Registry Number 104-67-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isovaleric acid, CAS Registry Number 503-74-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-nonalactone, CAS Registry Number 104-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Virus‐Dependent Geographic Structure of Co‐Circulating Viruses in a Single Bat Species - Avery L. Holmes; Alice Broos; Daniel J. Becker; Jorge E. Carrera; Maxwell J. Farrell; Rita Ribeiro; Carlos Tello; Laura M. Bergner; Daniel G. Streicker (Molecular Ecology, 2026)
Understanding the spatial spread of viruses within wildlife populations is often a key component of disease management efforts. Viral spread is likely constrained by host ecology, but inter‐virus differences in infection strategy might allow some viruses to overcome these constraints, leading to divergent population structures within a common host environment. We studied the phylogeographic structure of six virus taxa (dependoparvovirus, deltavirus, mastadenovirus, betaherpesvirus and two lineages of rabies virus) circulating in common vampire bats ( Desmodus rotundus ) in Peru, finding that viral population structure is inconsistently constrained by host ecology. Specifically, while bat travel distance structured the genetic diversity of betaherpesvirus and two lineages of rabies virus, other viruses were instead constrained by anthropogenic factors (dependoparvovirus), or had weakly defined population structure (mastadenovirus). The genetic structure of all viruses was affected by a measure of human travel difficulty between sites, but effects varied in size and direction. Distinct drivers of viral population structure within the same host species imply that virus infection strategy can outweigh host ecological connectivity, acting as a key determinant of geographic spread. Because barriers to gene flow generalise poorly between viruses, whether a tractable virus can illuminate host population structure or predict the spread of high‐impact viruses depends on individual virus biology.

Beyond macrophages: FIPV tropism includes T and B lymphocytes - Aadhavan Balakumar; Patrawin Wanakumjorn; Kazuto Kimura; Ehren McLarty; Katherine Farrell; Terza Brostoff; Jully Pires; Tamar Cohen-Davidyan; Jennifer M. Cassano; Brian Murphy; Krystle Reagan; Amir Kol (Veterinary Microbiology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

2nd update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,6-nonadien-3-ol, CAS Registry Number 10339-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, linalool, CAS Registry number 78-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2H-indeno[4,5b] furan, decahydro-2,2,6,6,7,8,8-heptamethyl, CAS Registry Number 476332-65-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-dodecalactone, CAS Registry Number 2305-05-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, palmitic acid, CAS Registry number 57-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2,6,8-trimethylnonan-4-one, CAS Registry Number 123-18-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyric acid, CAS Registry number 116-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,8-dimethyl-4,9-decadienal, CAS Registry number 71077-31-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedrene, CAS Registry Number 11028-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 5-methyl-3-heptanone, CAS Registry Number 541-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, iris pallida oil, CAS registry number 8002-73-1, RIFM ID 265.A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 8H-indeno(4,5-B)furan,2,3,3a,4,5,5a,6,7,8a,9-decahydro-2,6,6,7,8,8-hexamethyl mixture of isomers, CAS Registry Number 338735-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-nonanone, CAS Registry Number 821-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-undecanone, CAS Registry Number 112-12-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-octanone, CAS registry number 106-68-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-decanone, CAS Registry Number 693-54-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-heptanone, CAS Registry Number 110-43-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-heptalactone, CAS Registry Number CAS # 105-21-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-valerolactone, CAS Registry Number 108-29-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, lauric acid, CAS Registry Number 143-07-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-octanone, CAS Registry Number 111-13-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, benzoin infusion, Sumatra, CAS Registry Number 9000-05-9, RIFM ID 104-K2.31 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-heptanone, CAS Registry Number 123-19-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-heptanone, CAS Registry Number 106-35-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, myrtenol, CAS Registry Number 515-00-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylpropionic acid, CAS registry number 501-52-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexyl phenylacetate, CAS Registry Number 5421-17-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl cyclohexadiene (mixture of isomers), CAS Registry Number 30640-46-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanoic acid, CAS Registry Number 334-48-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 5-methyl-5-propyl-2-(1-methylbutyl)-1,3-dioxan, CAS Registry Number 80480-24-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanoic acid, CAS Registry Number 124-07-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-isopropylacetophenone, CAS Registry Number 645-13-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonanoic acid, CAS Registry Number 112-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4H-4a,9-methanoazuleno[5,6-d]-1,3-dioxole, octahydro-2,2,5,8,8,9a-hexamethyl-, (4aR,5R,7aS,9R)-, CAS Registry Number 211299-54-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, spiro[5.5]undec-8-en-1-one, 2,2,7,9-tetramethyl-, CAS Registry Number 502847-01-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-tolyl 3-methylcrotonate, CAS Registry Number 24700-20-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexanoic acid, CAS Registry Number 142-62-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-1,3-dioxolane, CAS Registry Number 33941-99-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-hydroxyacetophenone, CAS Registry Number CAS # 118-93-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-isopropyl-2-methoxy-1-methylbenzene, CAS Registry Number 6379-73-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1-ethynylcyclohexyl acetate, CAS Registry Number 5240-32-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,5,9b-tetrahydroindeno[1,2-d]-1,3-dioxine, CAS Registry Number 18096-62-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenyl-1-propanol, CAS Registry Number 122-97-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzaldehyde, CAS Registry Number 100-52-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Recognizing, reinforcing, and strengthening community capacity through researcher–community partnerships: insights from EPA researchers’ engagements with communities in four US waterscapes - Megan Dwyer Baumann; Kathleen C. Williams; Emily Eisenhauer; Desiree Farrell; Jenna M. Hartley; Meghan R. Klasic; A. Marissa Matsler; Candace K. May; Leah M. Sharpe; Abigail Sullivan; Kara Takasaki; Kathleen Torso; et al. (Socio-Ecological Practice Research, 2025)

The CALHM1 blocker CGP37157 increases seizure severity during status epilepticus in adult mice - Meghma Mitra; Amaya Sanz Rodriguez; Norman Delanty; Alan Beausang; Francesca M. Brett; Michael A. Farrell; Jane Cryan; Donncha F. O’Brien; David Henshall; Maria F. Cano-Abad; Tobias Engel (Purinergic Signalling, 2025)
Epilepsy is one of the most common chronic brain diseases affecting up to 70 million people worldwide. Major challenges of epilepsy treatment include the high pharmacoresistance in patients and the lack of disease-modification. Extracellular adenosine 3’triphosphate (ATP), a key neurotransmitter in the activation of the purinergic signalling system, is increasingly recognized to contribute to pathological brain hyperexcitability in epilepsy. Consequently, targeting ATP-release mechanisms may constitute a new therapeutic strategy for seizure control and epilepsy. The calcium channel, Calcium Homeostasis Modulator 1 (CALHM1), a voltage-gated, non-selective ion channel that permits the passage of various cations and small molecules, is expressed in neurons and plays an essential role during neuronal excitability and neurotransmission. In addition to ions, CALHM1 also allows the passage of ATP into the extracellular space, activating thereby purinergic receptors. Here, we tested if the pharmacological blocking of CALHM1 via CGP37157 (7-chloro-5-(2-chlorophenyl)-3,5-dihydro-4,1-benzothiazepin-2-(1H)-one) alters the severity of intra-amygdala kainic acid-induced status epilepticus. Our results show that CGP37157 increased the severity of seizures during status epilepticus. In addition, CALHM1 protein levels are down-regulated in the hippocampus in epileptic mice and Temporal Lobe Epilepsy (TLE) patients. In summary, our results identify CALHM1 as a new contributor to seizures and suggest targeting of CALHM1 as new treatment strategy for epilepsy.

On the equatorial dayside ionosphere of Saturn – In-situ observations give evidence for a dynamic and layered structure in disequilibrium - J.-E. Wahlund; A.I. Eriksson; M.W. Morooka; S. Buchert; M. Persson; E. Vigren; J. Dreyer; W.S. Kurth; J.H. Jr Waite; J.-P. Lebreton; W.M. Farrell; I. Müller-Wodarg (Icarus, 2025)

Abundance Trends of Pacific Salmon During a Quarter Century of ESA Protection - Michael J. Ford; Steven T. Lindley; Katie A. Barnas; Andrew O. Shelton; Brian C. Spence; Laurie A. Weitkamp; Damon M. Holzer; David A. Boughton; Elizabeth E. Holmes; James M. Myers; Chris E. Jordan; Heidi Fish; et al. (Fish and Fisheries, 2025)
Between 1989 and 2007, 28 Distinct Population Segments (DPS) of Pacific salmon ( Oncorhynchus spp.) spawning in rivers in California and the Pacific Northwest (Oregon, Washington, Idaho) were listed (protected) under the US Endangered Species Act (ESA). In the roughly 25 years since then, considerable efforts have been made to recover these populations, but no DPS has increased sufficiently to be delisted. We evaluated abundance trends of ESA‐listed Pacific salmon DPS, along with DPS that were not ESA‐listed. Our goal was to evaluate whether protected DPS increased in abundance during the period of protection (nominally 1995–2020 in our study), either in absolute terms or relative to the unprotected DPS. A majority of the protected DPS had increasing abundance trends over this time period, and protected populations had higher median trends than non‐protected populations of the same species. Geographically, populations in the Pacific Northwest had higher median trends than those in California. Among species of protected populations, Chinook salmon ( O. tshawytscha ), chum salmon ( O. keta ) and sockeye salmon ( O. nerka ) had higher median trends than coho salmon ( O. kisutch ) and steelhead (anadromous O. mykiss ). For most DPS (listed and unlisted), trends in harvest rates and hatchery releases were relatively stable during the same time period, whereas trends in indicators related to freshwater and marine climate were generally negative for salmon. Our results suggest that salmon recovery actions may have helped to stabilise and increase protected DPS, but most remain far below their recovery goals.

RIFM fragrance ingredient safety assessment, benzeneacetonitrile, a-butylidene-, (Z), CAS Registry Number 130786-09-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, geraniol, CAS registry number 106-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenoxyethanol, CAS Registry number 122-99-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, cinnamyl alcohol, CAS Registry Number 104-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl alcohol, CAS Registry Number 100-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-[[3-(4-methoxyphenyl)-2-methylpropylidene]amino]-, methyl ester, CAS registry number 111753-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, 4-carvomenthenol, CAS Registry Number 562-74-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-tert-butylcyclohexyl acetate, CAS registry number 88-41-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-tert-butylcyclohexyl acetate, CAS Registry Number 31846-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-tert-butylcyclohexyl acetate, CAS Registry Number 32210-23-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

A higher-order finite-element implementation of the nonlinear Fokker–Planck collision operator for charged particle collisions in a low density plasma - M.R. Hardman; M. Abazorius; J. Omotani; M. Barnes; S.L. Newton; J.W.S. Cook; P.E. Farrell; F.I. Parra (Computer Physics Communications, 2025)

Factors affecting short-term post-release survival probability of Lake Trout implanted with acoustic telemetry transmitters - Alexander J. Gatch; Dimitry Gorsky; Kyle T. Morton; R. Josephine Johnson; Collin J. Farrell; Timothy B. Johnson; Emma J. Bloomfield; Brent Metcalfe; Jessica Goretzke; Michael Connerton; Sarah M. Larocque; Jonathan D. Midwood; et al. (Fisheries Research, 2025)

Assessment of CYP2D6 gene expression in liver tissue: Variability in CYP2D6 mRNA levels within genotype-predicted metabolizer phenotype groups - Erika L. Meaddough; Sara M. Sarasua; Deborah Kunkel; Luigi Boccuto; Satishkumar R. Ganakammal; Matt Moersen; Christopher L. Farrell (Chemico-Biological Interactions, 2025)

Expanding wildlife serosurveillance: a study of influenza A virus exposure in Irish carnivores - Paule-Emilie Ruy; Samantha Ball; Gerald Barry; Benoît Cuq; Allan D. McDevitt; Holly M. English; Maeve Louise Farrell; Eamonn Gormley; Ian O’Connor; Patricia Romero; Ana Vale; Katie O’Dwyer (European Journal of Wildlife Research, 2025)
Increasing reports of zoonotic avian influenza virus (AIV) spillovers to mammals signal critical shift in their ecology and raise substantial public health concerns. The highly pathogenic avian influenza H5N1 clade 2.3.4.4b has driven this expansion, with genetic adaptations enhancing replication in mammalian hosts. Adaptations have been identified in diverse carnivore species, including American mink ( Neogale vison ), red foxes ( Vulpes vulpes ), and otters ( Lutra lutra ). These carnivores often feed on, or share habitat with, wild birds, making them suitable species for monitoring AIV presence in mammals. Here we investigated exposure to influenza A viruses (IAVs), including H5 and H7 subtypes in three mesocarnivore species (red foxes, American mink, and European badgers) in Ireland. Using enzyme-linked immunosorbent assays, we detected a seroprevalence for IAVs of 24.6% (28/114) in foxes, 22.2% (2/9) in mink, and 1% (1/96) in badgers. Among red fox samples positive for antibodies against IAVs, 82.1% (23/28) were positive for antibodies against the H5 subtype. No antibodies against the H7 subtype were detected. We also examined the use of Nobuto filter paper as a reliable alternative to serum samples for IAVs antibody detection via ELISA and assessed the use of haemolysed serum samples. These findings, as well as those gathered from ongoing passive surveillance of wild birds, highlight that influenza A is circulating in wildlife in Ireland. If we are to better understand influenza A dynamics in Ireland, and globally, it is imperative that surveillance programmes are supported, and serosurveys provide one valuable tool for active surveillance.

RIFM fragrance ingredient safety assessment, phenyl salicylate, CAS Registry Number 118-55-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, fenchone, CAS Registry Number 1195-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, phenethyl acetate, CAS registry number 103-45-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal diethyl acetal, CAS Registry Number 7779-94-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amylcyclohexyl acetate (mixed isomers), CAS Registry Number 67874-72-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanal dimethyl acetal, CAS Registry Number 10022-28-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl hexanoate, CAS Registry Number 7779-23-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylundecanal dimethyl acetal, CAS Registry Number 68141-17-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal dimethyl acetal, CAS Registry number 141-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-isobutylquinoline, CAS registry number 93-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-methyl quinoline, CAS registry number 91-63-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyisooctane, CAS Registry Number 69178-43-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonane, 1,1-diethoxy-, CAS Registry Number 54815-13-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1,1-diethoxy-3,5,5-trimethylhexane, CAS registry number 86198-35-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-(methylpropyl)quinoline, CAS registry number 1333-58-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanal dimethyl acetal, CAS Registry Number 7779-41-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-isopropylphenol, CAS Registry Number 99-89-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-buten-2-one, 4-(2,2,3-trimethyl-6-methylenecyclohexyl)-, CAS registry number 79-68-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, heptanal dimethyl acetal, CAS registry number 10032-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyhexane, CAS registry number 3658-93-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-acetyl-5-methylfuran, CAS Registry Number 1193-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isophytol, CAS Registry Number 505-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-furyl methyl ketone, CAS Registry Number 1192-62-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, savory winter oil, CAS Registry Number 90106-57-3, RIFM ID 1181-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho wood oil, CAS Registry Number 8022-91-1, RIFM ID 217-D2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, dimethylcyclohex-3-ene-1-carbaldehyde (isomer unspecified), CAS Registry Number 27939-60-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-2-(4-methyl-3-cyclohexen-1-yl)-5-hepten-2-ol, CAS Registry Number 515-69-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, maltol, CAS registry number 118-71-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-(5,5,6-trimethylbicyclo[2.2.1]hept-2-yl)cyclohexan-1-ol, CAS registry number 3407-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl valerate, CAS Registry Number 10361-39-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isocyclocitral, CAS Registry Number 1335-66-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, ho leaf oil, CAS Registry Number 8022-91-1, RIFM ID 217-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho bark oil, CAS registry number 8022-91-1, RIFM ID 217-C2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl formate, CAS Registry Number 104-57-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyheptane, CAS Registry Number 688-82-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-octanol, CAS registry number 111-87-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,6,7,8,8a-hexahydro-1,4-methanonaphthalen-5(1H)-one, CAS Registry Number 51519-65-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl hexanoate, CAS registry number 540-07-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, undecanal, CAS Registry Number 112-44-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, N-benzoylanthranilic acid, CAS Registry Number 579-93-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, undecyl alcohol, CAS Registry Number 112-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-tridecanol, CAS Registry Number 112-70-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, lauryl alcohol, CAS Registry Number 112-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, hexyl alcohol, CAS Registry Number 111-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl maltol, CAS Registry Number 4940-11-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyrophenone, CAS Registry Number 495-40-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, p-tolyl phenylacetate, CAS Registry Number 101-94-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl decanoate, CAS Registry Number 110-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-decanol, CAS registry number 112-30-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, clove bud absolute, CAS Registry Number 8000-34-8, RIFM ID 583-F2.1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nonyl alcohol, CAS Registry Number 143-08-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methoxy dicyclopentadiene carboxaldehyde, CAS Registry Number 86803-90-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, octahydro-4,7-methano-1H-indenecarbaldehyde, CAS Registry Number 30772-79-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, acetophenone, CAS Registry number 98-86-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, Sage oil, Spanish, CAS Registry Number 8022-56-8, RIFM ID 479-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

2nd Update to RIFM fragrance ingredient safety assessment, α-amylcinnamaldehyde, CAS Registry Number 122-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Corrigendum to “RIFM fragrance ingredient safety assessment, vanillin isobutyrate, CAS Registry Number 20665-85-4” [Food Chem. Toxicol. 197 Supplement 1 (2024) 115141 ISSN 0278–6915] - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, heptyl alcohol, CAS registry number 111-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-acetoxy-2,5-dimethyl-3(2H)furanone, CAS Registry Number 4166-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl propionate, CAS Registry Number 105-68-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl propionate, CAS Registry Number 540-42-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-(p-methoxyphenyl)-2-butanone, CAS Registry Number 104-20-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cis-6-nonenal, CAS registry number 2277-19-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylbutanal, CAS registry number 16251-77-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Temperature matters: Acute and latent toxicity of diluted bitumen to developing salmon is potentiated by a modest increase in water temperature - Derin M. Çalık; Feng Lin; Mackenzie Edgar; Anthony P. Farrell; Christopher J. Kennedy; Todd E. Gillis; Sarah L. Alderman (Aquatic Toxicology, 2025)

Diet and landscape controls on greenhouse gas emissions from cattle excreta in a semi-arid environment - Jiancan Liu; J. Diane Knight; Reynald L. Lemke; Helen M. Baulch; Richard E. Farrell (Agriculture, Ecosystems & Environment, 2025)

Isotopically resolved fate and processes of nitrogen in a constructed wetland treating domestic effluent - Danielle J. Allen; Mark Farrell; Wei Wen Wong; Jianyin Huang; Luke M. Mosley (Science of The Total Environment, 2025)

Update to RIFM fragrance ingredient safety assessment, cyclohexanepropanol, α-ethyl-2,2,6-trimethyl-, CAS Registry Number 60241-52-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl 3,7-dimethyl-6-octenoate, CAS registry number 2270-60-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (1aα,4α,7aα)-1a,3,3,4,6,6-hexamethyl-1a,2,3,4,5,6,7,7a-octahydronapth[3,3-b]oxirene, CAS Registry Number 94400-98-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cyclododecyl formate, CAS Registry Number 59052-82-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (Z)-4-dodecenal, CAS registry number 21944-98-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenylpropionaldehyde, CAS registry number 93-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4,5-dihydro-3(2H)thiophenone, CAS Registry Number 1003-04-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 9-undecenal, CAS Registry Number 143-14-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, β-methyl-benzenepentanal, CAS registry number 55066-49-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nonanal, CAS registry number 124-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-4-decen-1-al, CAS Registry Number 65405-70-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl formate, CAS Registry Number 110-45-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 8-undecenal, CAS registry number 58296-81-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl isovalerate, CAS Registry Number 1118-27-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, hexanal, CAS Registry Number 66-25-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,8-dimethyl-7-nonen-2-ol, CAS Registry Number 40596-76-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-ethoxy-4-(methoxymethyl)phenol, CAS Registry Number 5595-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, β-caryophyllene alcohol, CAS registry number 472-97-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, acetylcarene, CAS Registry Number 3608-11-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-heptenal, CAS Registry Number 6728-31-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl alcohol, CAS Registry Number 123-51-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-phenoxyethyl isobutyrate, CAS registry number 103-60-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl isobutyrate, CAS Registry Number 78-35-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-tetradecanol, CAS Registry Number 112-72-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-hexenoic acid, CAS Registry Number 4219-24-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl 2-nonynoate, CAS Registry Number 111-80-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-(4-methyl-3-cyclohexenyl)butanol, CAS Registry Number 15760-18-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, dihydro-β-ionol, CAS Registry Number 3293-47-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, p-tolylacetaldehyde, CAS Registry Number 104-09-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, β-pinene, CAS Registry Number 127-91-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, geranyl crotonate, CAS Registry Number 56172-46-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4(2,2,3-trimethyl-3-cyclopentenyl)butanol, CAS Registry Number 72089-08-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutyl valerate, CAS Registry Number 2050-09-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, octanal, CAS Registry Number 124-13-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, tricyclo[3.3.1.1.(3.7)]decan-2-ol, 4-methyl-8-methylene-, CAS Registry Number 122760-84-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, heptanal, CAS registry number 111-71-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl butyrate, CAS Registry Number 51115-64-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl alcohol, CAS Registry Number 71-41-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, pentanoic acid, 2-methylbutyl ester, CAS Registry Number 55590-83-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3,4-xylenol, CAS Registry Number 95-65-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl acetate, CAS Registry Number 624-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl butyrate, CAS Registry Number 539-90-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, decanal, CAS registry number 112-31-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedryl formate, CAS Registry Number 39900-38-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-(4-methoxyphenyl)-3-methylbutan-2-one, CAS Registry Number 67828-19-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-(p-methoxyphenyl)-2-propanone, CAS Registry Number 122-84-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-2-hexenyl acetate, CAS Registry Number 2497-18-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, isolongifolene oxide, CAS Registry Number 26619-69-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-menth-8-en-2-one, CAS Registry Number 7764-50-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, l-menthyl (R,S)-3-hydroxybutyrate, CAS Registry Number 108766-16-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyl alcohol, CAS registry number 71-36-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, tridecanal, CAS registry number 10486-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedr-8-ene epoxide, CAS Registry Number 13567-39-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, geranyl tiglate, CAS Registry Number 7785-33-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4′-tert-butyl-2′,6′-dimethylacetophenone, CAS Registry Number 2040-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl trans-2,cis-4-decadienoate, CAS registry number 3025-30-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl acetate, CAS Registry Number 123-92-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-hexadecanol, CAS Registry Number 36653-82-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl acetate, CAS Registry Number 110-19-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cis-3-hexenyl salicylate, CAS Registry Number 65405-77-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-2-hepten-6-ol, CAS registry number 1569-60-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nopyl acetate, CAS registry number 128-51-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl butyrate, CAS Registry Number 106-27-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, piperonal, CAS Registry Number 120-57-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzothiazole, CAS Registry Number 95-16-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-cyclopropylmethyl-4-methoxybenzene, CAS registry number 16510-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-2-methylenocta-6-enal, CAS registry number 22418-66-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl alcohol, CAS Registry Number 78-83-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylpropyl pentanoate, CAS Registry Number 10588-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-(3-heptyl)-1,3-dioxolane, CAS Registry Number 4359-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-methyl-3-pentenoate, CAS Registry Number 1617-23-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, vanillin isobutyrate, CAS Registry Number 20665-85-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutanal diethyl acetal, CAS Registry Number 3842-03-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Water-Level Variability Mediates Northern Pike Reproduction at Restored Coastal Habitats in the Upper St. Lawrence River, USA - John Paul Leblanc; John M. Farrell (Wetlands, 2025)

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

Does mycorrhizal colonization of biofilter plants improve their water uptake or drought resistance? - Kanglin Tian; Claire Farrell; Anna Lintern; Yussi M. Palacios; Christopher Szota; Brandon Winfrey (Urban Forestry & Urban Greening, 2025)

Characterisation and comparison of Mycoplasma bovis strain types from Irish and Scottish bovine isolates in a global context - C.I. McAloon; D. Farrell; J. Smith; S.V. Gordon; M. Sheehan; A. Kennedy; T. Geraghty; C. Mason; B. Leggett; F.C. Leonard; T. Sweeney; G. McGrath; et al. (Veterinary Microbiology, 2025)

Cover crops increase belowground N retention substantially in corn cropping systems: Results from a 15N residue swapping experiment - Spencer M. Heuchan; Claudia Wagner-Riddle; Khagendra R. Baral; Katelyn A. Congreves; Richard E. Farrell; Sean Jordan; Hugh A. L. Henry (Plant and Soil, 2025)

Improved nitrogen fertilizer management reduces nitrous oxide emissions in a northern Prairie cropland - D. Ferland; C. Wagner-Riddle; S.E. Brown; M. Bourgault; W. Helgason; R.E. Farrell; K.A. Congreves (Science of The Total Environment, 2024)

RIFM fragrance ingredient safety assessment, (4-methylphenoxy)acetaldehyde, CAS Registry Number 67845-46-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, propyl alcohol, CAS Registry Number 71-23-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dibenzyl ether, CAS Registry number 103-50-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, β-ionyl acetate, CAS Registry Number 22030-19-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cinnamyl cinnamate, CAS Registry Number 122-69-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6-xylenol, CAS Registry Number 576-26-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobutyl formate, CAS registry number 542-55-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl 2-octynoate, CAS Registry Number 111-12-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexanone 1,3-butylene glycol ketal, CAS Registry Number 6413-26-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, zingerone, CAS Registry Number 122-48-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-ethoxy-4-[(1-methylethoxy)methyl] phenol, CAS Registry number 96840-56-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, diethyl malonate, CAS registry number 105-53-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4,8-dimethylnona-3,7-dienyl)pyridine, CAS Registry Number 38462-23-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-propanediol, 2,2-dimethyl-, 1,3-diacetate, CAS registry number 13431-57-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-(cis-3-hexenyloxy)propanenitrile, CAS Registry Number 142653-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobutyl benzoate, CAS registry number 120-50-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4-methyl-3-penten-1-yl)-2(5H)-furanone, CAS Registry number 61315-75-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-butyl-4,4,6-trimethyl-1,3-dioxane, CAS registry number 54546-26-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-(2-tert-butyl cyclohexyloxy)-2-butanol, CAS Registry Number 139504-68-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-methylbutyrate, CAS Registry Number 7452-79-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzyl salicylate, CAS registry number 118-58-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl benzoate, CAS registry number 6789-88-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl isovalerate, CAS Registry Number 556-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, cyclohexanecarboxylic acid, CAS Registry Number 98-89-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl isobutyrate, CAS registry number 97-62-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6,8-dimethylnonan-2-ol, CAS registry number 70214-77-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoamyl benzoate, CAS registry number 94-46-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl isobutyrate, CAS registry number 547-63-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 10-undecenoic acid, heptyl ester, CAS registry number 68141-27-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-(4-methylcyclohex-3-enyl)-3-butenyl acetate, CAS registry number 6819-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-methyl-α-amyl cinnamic aldehyde, CAS Registry Number 84697-09-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl salicylate, CAS registry number 119-36-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl 2-methylbutyrate, CAS Registry Number 868-57-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, amyl salicylate, CAS Registry Number 2050-08-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-methyl-2-(1-methylpropyl)cyclohexyl acetate, CAS Registry number 72183-75-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis-3-hexenyl benzoate, CAS Registry Number 25152-85-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoamyl salicylate, CAS Registry Number 87-20-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-(1-methylethyl)-, trans-, CAS Registry Number 4625-90-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-2-pentanol, CAS registry number 108-11-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6-dimethyl-4-heptanol, CAS registry number 108-82-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, heptyl acetate, CAS registry number 112-06-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Applying trace element geochemistry of archaeological bone to study the coevolution of environmental change and human health in the Roman Empire - Sean R. Scott; Martin M. Shafer; Joel T. Overdier; Maria E. Teschler-Nicola; Peter C. Ramsl; Barry Cunliffe; Philip M. Farrell (Environmental Research, 2024)

Temporary atmospheres produced by human activities on the Moon - Rosemary M. Killen; Benjamin T. Sprague; William M. Farrell (Advances in Space Research, 2024)

Comparison of antimicrobial resistant Enterobacterales isolates from the dairy production environment in low and high zinc containing regions - E. Anedda; E.A. Alexa; M.L. Farrell; M. Croffie; G. Madigan; D. Morris; C.M. Burgess (Science of The Total Environment, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-5-phenylpentanol, CAS Registry Number 25634-93-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl formate, CAS registry number 629-33-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl butyrate, CAS Registry Number 2639-63-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, furfural, CAS Registry Number 98-01-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl acetate, CAS Registry Number 112-14-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl formate, CAS registry number 112-32-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-ethyl-, trans-, CAS Registry Number 91069-40-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, p-mentha-1,8-dien-7-ol, CAS Registry Number 536-59-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 7-isopropyl-1,4-dimethylazulene, CAS registry number 489-84-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-isopropyl-1-methylcyclohexene, CAS registry number 29350-67-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl α-ionone, CAS Registry Number 79-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, lauryl acetate, CAS Registry Number 112-66-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-methyl-, CAS Registry number 94201-19-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-5-phenylpentanol, CAS Registry Number 55066-48-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, nonyl acetate, CAS registry number 143-13-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl butyrate, CAS Registry Number 110-39-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(methylthio)hexyl acetate, CAS registry number 51755-85-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,2-dimethyl-3-phenylpropanol, CAS registry number 13351-61-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-(cis-3-hexenyl)dihydro-5-methyl-2(3H)furanone, CAS Registry Number 70851-61-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-phenyl anisole, CAS registry number 86-26-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl acetate, CAS registry number 105-87-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl linalool, CAS registry number 1113-21-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ionone (mixed isomers), CAS registry number 8013-90-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl salicylate, CAS Registry Number 118-61-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-phenyl-3-buten-2-ol, CAS registry number 17488-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isopropyl acetate, CAS registry number 108-21-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl propionate, CAS Registry Number 2445-76-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-butylcinnamaldehyde, CAS registry number 7492-44-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, decyl acetate, CAS Registry Number 112-17-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, musk ketone, CAS registry number 81-14-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, veratraldehyde, CAS Registry Number 120-14-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isopropyl butyrate, CAS Registry Number 638-11-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-hydroxybenzoic acid, CAS Registry Number 69-72-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methylfurfural, CAS registry number 620-02-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl acetate, CAS registry number 142-92-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenylpentanol, CAS registry number 92585-24-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4-phenylbutyraldehyde, CAS Registry Number 40654-82-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis-3-hexenal, CAS Registry Number 6789-80-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, pinus nigra oil, CAS Registry Number 8000-26-8, RIFM ID 1068-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexyl phenylacetate, CAS Registry Number 42288-75-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,4,5,6,6-pentamethylheptan-2-ol, CAS registry number 87118-95-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-cyclohexadiene-1-carboxylic acid, 4,6,6-trimethyl-, ethyl ester, CAS Registry Number 100520-15-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2(4H)-benzofuranone, 5,6-dihydro-3,6-dimethyl-, CAS Registry Number 80417-97-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, β-methylphenethyl alcohol, CAS Registry Number 1123-85-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, N-ethyl-N-(3-methylphenyl)propionamide, CAS Registry Number 179911-08-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl cinnamate, CAS Registry number 1866-31-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-hexene, 1-[(2-methyl-2-propenyl)oxy]- (3Z)-, CAS Registry Number 292605-05-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, lavandin abrialis, CAS registry number 8022-15-9, RIFM ID 1048554 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, rotundone, CAS Registry Number 18374-76-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methylheptenol, CAS Registry Number 1335-09-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,4-bis(ethoxymethyl)cyclohexane, CAS Registry Number 54889-63-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, bicyclo[2.2.1]heptan-2-ol, 1,3,3-trimethyl-, benzoate, CAS Registry Number 55066-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methylbutyl hexanoate, CAS registry Number 2601-13-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, propanoic acid, 2-methyl-, cyclohexyl ester, CAS Registry Number 1129-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,6-nonadien-3-yl acetate, CAS Registry Number 61931-80-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-heptanol, 3,6-dimethyl-, CAS registry number 1247790-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl cyclohexanecarboxylate, CAS Registry Number 3289-28-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl butyrate, CAS Registry Number 78-36-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6-butyl-2,4-dimethyldihydropyrane, CAS Registry Number 24237-00-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-7-methoxyoctan-2-ol, CAS registry number 41890-92-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-isopropyl-N,2,3-trimethylbutyramide, CAS registry number 51115-67-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, piperonyl acetate, CAS registry number 326-61-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-propylphenethyl alcohol, CAS registry number 705-73-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl heptanoate, CAS registry number 142-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-(4-methylphenoxy)ethanol, CAS Registry Number 15149-10-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nonanoyl 4-hydroxy-3-methoxybenzylamide, CAS Registry Number 2444-46-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl hexanoate, CAS Registry Number 123-68-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenethyl alcohol, CAS Registry Number 60-12-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, benzenepropanol, a,ß-dimethyl-, CAS Registry Number 56836-93-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(2-oxopropyl)-2-pentylcyclopentanone, CAS Registry Number 40942-73-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1,3,3-trimethyl-2-norbornanyl acetate, CAS registry number 13851-11-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, tetrahydrogeranial, CAS Registry Number 5988-91-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isobornyl acetate, CAS Registry Number 125-12-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nerolidyl acetate (isomer unspecified), CAS registry number 2306-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, oxacyclohexadecane-2,13-dione, CAS registry number 38223-29-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, (Z)-octadec-9-enol, CAS registry number 143-28-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, linalyl acetate, CAS registry number 115-95-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-naphthalenol, 1,2,3,4,4a,5,8,8a-octahydro-2,2,6,8-tetramethyl-, CAS Registry Number 103614-86-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-5-yl pivalate, CAS Registry Number 68039-45-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-5-yl isobutyrate, CAS Registry Number 67634-20-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, tricyclodecanyl acetate, CAS registry number 64001-15-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobornyl propionate, CAS Registry Number 2756-56-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl octanoate, CAS Registry Number 4230-97-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl formate, CAS registry number 115-99-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nerol oxide, CAS Registry Number 1786-08-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, l-menthyl D-lactate, CAS registry number 59259-38-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl propionate, CAS registry number 144-39-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, trichloromethyl phenyl carbinyl acetate, CAS Registry number 90-17-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

The relationship between total organic carbon and bottom water redox state in North American black shales - Samantha R. Ritzer; Shane Schoepfer; Bella Bussian; Una C. Farrell; Tiffani Fraser; Charles M. Henderson; Junyao Kang; Chiza N. Mwinde; Austin Patch; Erik A. Sperling (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-hexen-1-ol, 5-methyl-2-(1-methylethenyl)-, CAS registry number 58461-27-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, dihydro-α-terpineol, CAS Registry Number 498-81-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-hexylcyclopentanone, CAS registry number 13074-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butyl isobutyrate, CAS registry number 10031-71-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, d,l-menthone 1,2-glycerol ketal, CAS Registry Number 63187-91-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-cyclohexyl-2-methyl-2-butanol, CAS registry number 83926-73-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4′-hydroxy-3′-methoxyacetophenone, CAS Registry Number 498-02-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2,2,4-trimethyl-4-phenyl-butane-nitrile, CAS Registry Number 75490-39-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, thymol, CAS Registry Number 89-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl cinnamate, CAS Registry Number 103-36-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-2-butenyl benzoate, CAS Registry Number 5205-11-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methylcyclooctyl carbonate, CAS Registry Number 61699-38-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-p-tolylethanol, CAS registry number 699-02-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,3,6-octatriene, CAS Registry Number 13877-91-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,1-dimethyl-2-phenylethyl isobutyrate, CAS Registry Number 59354-71-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, amyl cinnamate, CAS Registry Number 3487-99-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butanol, CAS Registry Number 103-05-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, benzenepropanenitrile, 4-ethyl-α,α.-dimethyl-, CAS Registry Number 134123-93-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl 2,4-dihydroxy-m-toluate, CAS Registry Number 33662-58-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2H-1,5-benzodioxepin-3(4H)-one, 7-(1-methylethyl)-, CAS Registry Number 950919-28-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-ethylhexanoate, CAS Registry Number 2983-37-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexyl salicylate, CAS registry number 25485-88-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment,α-methylbenzyl alcohol, CAS registry number 98-85-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-isopropylcyclohexanol, CAS Registry Number 4621-04-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, acetaldehyde, diphenethyl acetal, CAS Registry Number 122-71-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, α,α-dimethylphenethyl alcohol, CAS Registry Number 100-86-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, citronellyl ethyl oxalate, CAS Registry Number 60788-25-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-tert-butylcyclohexyl carbonate, CAS Registry Number 67801-64-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2,3,6-trimethylcyclohexyl carbonate, CAS Registry Number 93981-50-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-octyl acetate, CAS registry number 4864-61-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, exo-2-[(1,7,7-trimethylbicyclo[2.2.1]hept-2-yl)oxy]ethanol, CAS Registry Number 7070-15-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-propanol, reaction products with boron trifluoride and 5-ethylidenebicyclo[2.2.1]hept-2-ene, CAS registry number 90530-04-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1-propanol, 2-methyl-3-[(1,7,7-trimethylbicyclo-[2.2.1]hept-2-yl)oxy]-, CAS Registry Number 128119-70-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-nonanediol acetate (mixed esters), CAS Registry Number 1322-17-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,12-tridecadienenitrile, CAS Registry Number 134769-33-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexanoic acid, 4-methyl-, CAS registry number 1561-11-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-ethyloctanoic acid, CAS registry number 16493-80-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylhexanoic acid, CAS registry number 4536-23-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylheptanoic acid, CAS registry number 1188-02-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, butyl 2-methylvalerate, CAS Registry Number 6297-41-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, N,N-diethyloctamide, CAS registry number 996-97-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenethyl salicylate, CAS Registry Number 87-22-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzonitrile, 3,4-dimethyl-, CAS Registry Number 22884-95-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-allyl-2-methoxyphenyl benzyl ether, CAS Registry Number 57371-42-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,6-nonadien-1-ol, CAS Registry Number 76649-25-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-methylpentanoate, CAS Registry Number 39255-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, linalyl cinnamate, CAS registry number 78-37-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 3,5,5-trimethylhexanoate, CAS Registry Number 67707-75-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methyloctanoic acid, CAS Registry Number 54947-74-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyl 10-undecenoate, CAS Registry Number 109-42-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylvaleric acid, CAS Registry Number 97-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-methylpentanoic acid, CAS registry number 105-43-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methylnonanoic acid, CAS Registry Number 45019-28-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-ethylbutyric acid, CAS Registry Number 88-09-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis- and trans-p-1(7),8-menthadien-2-yl acetate, CAS registry number 71660-03-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, diethyldimethylcyclohex-2-en-1-one, CAS Registry Number 68845-36-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-phenyl-3-buten-1-yl acetate, CAS Registry Number 7306-12-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, spiro[1,3-dioxolane-2,8′(5′H)-[2H-2,4a]methanonaphthalene],hexahydro-1′,1′,5′,5′-tetramethyl-, [2′S-(2′α,4′aα,8′aα)]-, CAS Registry Number 154171-77-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, p-tolyl alcohol, CAS Registry Number 589-18-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methylpentanoic acid, CAS Registry Number 646-07-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-ethyl-2,3,4,5-tetramethylcyclohexen-1-one, CAS Registry Number 17369-60-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexanol, 2-methoxy-4-propyl-, CAS Registry Number 23950-98-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 10-undecenoate, CAS Registry Number 692-86-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-tert-butyldihydrocinnamaldehyde, CAS Registry Number 18127-01-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isoeugenyl phenylacetate, CAS registry number 120-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Ritualized male–male combat resulting from intraspecific food competition in three Agkistrodon species - Terence M. Farrell; Henderson C. Gull; Frederick S. Boyce; Stephen C. Richter (Journal of Ethology, 2024)

RIFM fragrance ingredient safety assessment, 3-(p-isopropylphenyl)propionaldehyde, CAS registry number 7775-00-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,3,5-trimethylcyclohexyl ethyl ether, CAS Registry Number 67583-77-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, triethyltrimethyl-2-cyclohexen-1-one, CAS Registry Number 68845-35-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, germacrene D, CAS Registry Number 23986-74-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methyl-2-thiophenecarboxaldehyde, CAS registry number 13679-70-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isoeugenyl benzyl ether, CAS Registry Number 120-11-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, pentyl benzoate, CAS Registry Number 2049-96-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl vanillin isobutyrate, CAS Registry Number 188417-26-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, l-carvone, CAS Registry Number 6485-40-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyl benzoate, CAS Registry Number 136-60-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-isopropyl phenylacetaldehyde, CAS Registry Number 4395-92-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl benzoate, CAS Registry Number 93-58-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-(1,1-dimethylpropyl)-4-ethoxy-, cis-, CAS Registry Number 181258-87-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-3-decen-5-ol, CAS Registry Number 81782-77-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoeugenol, CAS registry number 97-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 10-undecen-1-yl acetate, CAS Registry Number 112-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-2-pentenoic acid, CAS Registry Number 16957-70-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6,10-dodecadienal, 3,7,11-trimethyl-, (3S,6E)-, CAS registry number 194934-66-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, cuminyl nitrile, CAS registry number 13816-33-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (Z,Z)-1,1'-[ethylidenebis(oxy)]di(hex-3-ene), CAS Registry number 63449-64-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl benzoate, CAS Registry Number 93-89-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methyl-5-phenyl-3-hexanone, CAS Registry Number 4927-36-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (E)-1-(1-methoxypropoxy)hex-3-ene, CAS Registry Number 97358-54-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl undec-10-enoate, CAS registry number 111-81-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, acetaldehyde ethyl cis-3-hexenyl acetal, CAS Registry Number 28069-74-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-amylcinnamaldehyde, CAS Registry Number 122-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 9-decenyl acetate, CAS Registry Number 50816-18-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenol, 4-(3,6-dihydro-4-methyl-2H-pyran-2-yl)-2-methoxy-, CAS Registry Number 128489-02-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, eucalyptol, CAS Registry Number 470-82-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, pyridine, 5-hexyl-2-methyl-, CAS Registry Number 710-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dodecahydro-3,8,8,11a-tetramethyl-5H-3,5a-epoxynaphth[2,1-c]oxepin, CAS Registry Number 57345-19-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-3-buten-2-ol, CAS Registry Number 115-18-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-toluenethiol, CAS Registry Number 137-06-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-hydroxy-5-methyl-, methyl ester, CAS Registry Number 22717-57-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalool oxide, CAS Registry Number 1365-19-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

A multinational survey of companion animal veterinary clinicians: How can antimicrobial stewardship guidelines be optimised for the target stakeholder? - S. Farrell; A.F. Bagcigil; S.C. Chaintoutis; C. Firth; F.G. Aydin; C. Hare; M. Maaland; A. Mateus; A.P. Vale; U. Windahl; P. Damborg; D. Timofte; et al. (The Veterinary Journal, 2024)

Flow induced attrition of cellulose nanocrystals - Bradley P. Sutliff; Connor Farrell; Stephen M. Martin; Michael J. Bortner (Carbohydrate Polymers, 2023)

Novel insight into ammonium, phosphate, and iron(II) dynamics in the sediment porewater of a constructed wetland under artificial aeration through the diffusive equilibrium in thin films technique - Danielle J. Allen; Jianyin Huang; Mark Farrell; Luke M. Mosley (Environmental Research, 2023)

Gill net catchability of walleye (Sander vitreus): Are provincial standards suitable for estimating adult density outside the region? - Adam G. Hansen; Michael W. Miller; Erik T. Cristan; Collin J. Farrell; Paul Winkle; Mandi M. Brandt; Kyle D. Battige; Jesse M. Lepak (Fisheries Research, 2023)

Initial diet influences future development paths of gut microbiota in larval northern pike (Esox lucius) - Benjamin D. Gallo; John M. Farrell; Brian F. Leydet (Hydrobiologia, 2023)

Influence of water‐level variability on fish assemblage and natural reproduction following connectivity enhancement in a Typha‐dominated coastal wetland, USA - John Paul Leblanc; John M. Farrell (Journal of Fish Biology, 2023)
We evaluated a wetland habitat modification strategy to contrast fish assemblage structure and the production of young‐of‐the‐year (YOY) fish between different engineered habitats ( i.e ., spawning pool complexes and connectivity channels) relative to unmodified lateral channels in a large drowned river mouth tributary of the St Lawrence River. Prior to habitat modifications, the coastal wetland was impaired by water level regulations and dominance of the invasive hybrid cattail, Typha × glauca , which collectively replaced or created barriers to seasonally flooded spawning habitats important to fish. Connectivity enhancements provided fish access along a wetland habitat gradient from sedge‐meadows to the deeper water robust emergent main channel. Across an 8‐year fish emigration dataset (2012, 2013, 2016–2021) more than 90% of all captured fish ( N total = 218,086 fish) were YOY and modified habitats outperformed the unmodified channels in total fish catch‐per‐unit‐effort (CPUE) per year (both YOY and non‐YOY). Spawning pool complexes had higher YOY species richness than unmodified channel habitats. Fish assemblage structure differed between the modified habitats, where connectivity channels and unmodified channels shared a more similar fish assemblage than spawning pool complexes. Modified habitats, however, supported warmer water and higher dissolved oxygen than the unmodified channels. Redundancy analysis and linear mixed‐effect modelling with abiotic variables (hydrology, temperature and dissolved oxygen) showed significant effects on fish assemblage structure, species richness and CPUE of fish emigrating from the modified and unmodified habitats. Historic flooding in 2017 and 2019 was a primary driver of YOY fish production and fish assemblage structure, but also appeared to be associated with near anoxic conditions systemwide. YOY fish for several species was inversely affected by floods at spawning pool complexes, but CPUE of YOY fish for these species appeared unaffected at the connectivity channels despite low dissolved oxygen. Diversified habitat structure ( i.e ., connectivity channels and spawning pool complexes) offers a management option to enhance habitat for fish that allowed compensatory effects on the capture of YOY fish of several species during floods. This multifaceted outcome from the habitat modifications resulted in unique fish assemblages between the channelized and spawning pool habitat. A connectivity‐based habitat enhancement strategy provides adaptability for an uncertain climatic and regulatory future for the Laurentian Great Lakes and St Lawrence River.

Assessing Antigen-Adjuvant Complex Stability Against Physical Stresses By wNMR - Marc B. Taraban; Katharine T. Briggs; Yihua Bruce Yu; Michael T. Jones; Lindsey Rosner; Akhilesh Bhambhani; Donna M. Williams; Christopher Farrell; Mikhail Reibarkh; Yongchao Su (Pharmaceutical Research, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

A pilot study investigating feasibility of mainstreaming germline BRCA1 and BRCA2 testing in high-risk patients with breast and/or ovarian cancer in three tertiary Cancer Centres in Ireland - Terri Patricia McVeigh; Karl J. Sweeney; Donal J. Brennan; Una M. McVeigh; Simon Ward; Ann Strydom; Sheila Seal; Katherine Astbury; Paul Donnellan; Joanne Higgins; Maccon Keane; Michael J. Kerin; et al. (Familial Cancer, 2023)

Extreme eutrophication and salinisation in the Coorong estuarine-lagoon ecosystem of Australia's largest river basin (Murray-Darling) - L.M. Mosley; S. Priestley; J. Brookes; S. Dittmann; J. Farkaš; M. Farrell; A.J. Ferguson; M. Gibbs; M. Hipsey; J. Huang; O. Lam-Gordillo; S.L. Simpson; et al. (Marine Pollution Bulletin, 2023)

Evaluating the impact of heavy metals on antimicrobial resistance in the primary food production environment: A scoping review - Elena Anedda; Maeve Louise Farrell; Dearbháile Morris; Catherine M. Burgess (Environmental Pollution, 2023)

Millennial-scale drivers of small mammal isotopic niche dynamics in southern California - Nathaniel S. Fox; John R. Southon; Carrie M. Howard; Gary T. Takeuchi; Stephany Potze; Aisling B. Farrell; Emily L. Lindsey; Jessica L. Blois (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The interplay of temperature and algal enrichment intensifies bioturbation of the intertidal amphipod Corophium volutator - Eilish M. Farrell; Jan Beermann; Andreas Neumann; Alexa Wrede (Journal of Experimental Marine Biology and Ecology, 2023)

Reconciling climate action with the need for biodiversity protection, restoration and rehabilitation - Courtney E. Gorman; Andrew Torsney; Aoibheann Gaughran; Caroline M. McKeon; Catherine A. Farrell; Cian White; Ian Donohue; Jane C. Stout; Yvonne M. Buckley (Science of The Total Environment, 2023)

Artificial aeration of an overloaded constructed wetland improves hypoxia but does not ameliorate high nitrogen loads - Danielle J. Allen; Mark Farrell; Jianyin Huang; Simon Plush; Luke M. Mosley (Journal of Environmental Management, 2023)

From COVID-19 to Green Recovery with natural capital accounting - Michael Vardon; Paul Lucas; Steve Bass; Matthew Agarwala; Andrea M. Bassi; Diane Coyle; Anthony Dvarskas; Catherine A. Farrell; Oliver Greenfield; Steven King; Martin Lok; Carl Obst; et al. (Ambio, 2023)
The COVID-19 pandemic and related social and economic emergencies induced massive public spending and increased global debt. Economic recovery is now an opportunity to rebuild natural capital alongside financial, physical, social and human capital, for long-term societal benefit. Yet, current decision-making is dominated by economic imperatives and information systems that do not consider society’s dependence on natural capital and the ecosystem services it provides. New international standards for natural capital accounting (NCA) are now available to integrate environmental information into government decision-making. By revealing the effects of policies that influence natural capital, NCA supports identification, implementation and monitoring of Green Recovery pathways, including where environment and economy are most positively interlinked.

A Web-based Lifestyle Intervention for Cancer Survivors: Feasibility and Acceptability of SurvivorSHINE - Victoria A. Williams; Nashira I. Brown; Roman Johnson; M. Cole Ainsworth; David Farrell; Margaux Barnes; Suzanne Perumean-Chaney; Kevin Fontaine; Michelle Y. Martin; Dori Pekmezi; Wendy Demark-Wahnefried (Journal of Cancer Education, 2022)

Stable carbon and nitrogen isotopes explain methylmercury concentrations in stream food webs of Lake George, New York (USA) - M. W. Swinton; P. K. Myer; M. F. Schaller; E. A. Pettitt; J. L. Farrell; S. A. Nierzwicki-Bauer (Ecotoxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Disturbance is complicated: Headward‐eroding saltmarsh creeks produce multiple responses and recovery trajectories - Fengrun Wu; Steven C. Pennings; Collin Ortals; Jennifer Ruiz; W. Reilly Farrell; Samuel M. McNichol; Christine Angelini; Amanda C. Spivak; Merryl Alber; Chunfu Tong (Limnology and Oceanography, 2022)
Disturbances are one of the most important processes affecting natural systems, but there is a gap between simple conceptual models of disturbance and complex empirical studies. We studied the perturbation caused by headward‐eroding creeks in southeastern USA salt marshes. We measured disturbance responses (magnitude and recovery trajectory) of 19 variables. Some variables (shoot density, root biomass, snail density, soil pH, soil strength, soil temperature, elevation) declined sharply, while other variables (crab burrow density, soil organic matter, soil redox) increased sharply, in response to the burrowed and grazed conditions at the creek head. These variables recovered over subsequent years or decades. Other variables (shoot height, aboveground biomass, rhizome biomass, light interception) declined sharply in the creek head, then overshot control values before recovering. Some variables (benthic algae, soil salinity) did not appear to be disturbed by the creek head. As hypothesized, plants recovered before soils and snails. Disturbance magnitude and time to recovery were often greater directly adjacent to the new creekbank than for the same variables in a parallel transect further away from the creekbank, and in some cases variables never converged with control values, indicating a persistent state change. Reducing the dimensionality of the data set into principal component axes obscured the diverse ways in which different aspects of the system responded to and recovered from the perturbation. Our study illustrates the challenges in moving from simple conceptual models of disturbance to empirical studies in which multiple variables are likely to be affected differently and follow different recovery trajectories.

Host‐pathogen‐environment interactions predict survival outcomes of adult sockeye salmon ( Oncorhynchus nerka ) released from fisheries - Amy K. Teffer; Scott G. Hinch; Kristina M. Miller; David. A. Patterson; Arthur L. Bass; Steven J. Cooke; Anthony P. Farrell; Terry D. Beacham; Jacqueline M. Chapman; Francis Juanes (Molecular Ecology, 2022)
Incorporating host‐pathogen(s)‐environment axes into management and conservation planning is critical to preserving species in a warming climate. However, the role pathogens play in host stress resilience remains largely unexplored in wild animal populations. We experimentally characterized how independent and cumulative stressors (fisheries handling, high water temperature) and natural infections affected the health and longevity of released wild adult sockeye salmon ( Oncorhynchus nerka ) in British Columbia, Canada. Returning adults were collected before and after entering the Fraser River, yielding marine‐ and river‐collected groups, respectively ( N = 185). Fish were exposed to a mild (seine) or severe (gill net) fishery treatment at collection, and then held in flow‐through freshwater tanks for up to four weeks at historical (14°C) or projected migration temperatures (18°C). Using weekly nonlethal gill biopsies and high‐throughput qPCR, we quantified loads of up to 46 pathogens with host stress and immune gene expression. Marine‐collected fish had less severe infections than river‐collected fish, a short migration distance (100 km, 5–7 days) that produced profound infection differences. At 14°C, river‐collected fish survived 1–2 weeks less than marine‐collected fish. All fish held at 18°C died within 4 weeks unless they experienced minimal handling. Gene expression correlated with infections in river‐collected fish, while marine‐collected fish were more stressor‐responsive. Cumulative stressors were detrimental regardless of infections or collection location, probably due to extreme physiological disturbance. Because river‐derived infections correlated with single stressor responses, river entry probably decreases stressor resilience of adult salmon by altering both physiology and pathogen burdens, which redirect host responses toward disease resistance.

Keystone Perennial Grassland Species Control Soil Nitrogen Flows - Mark Farrell; Suzanne M. Prober (Ecosystems, 2021)

Intraspecific variation in tolerance of warming in fishes - David J. McKenzie; Yangfan Zhang; Erika J. Eliason; Patricia M. Schulte; Guy Claireaux; Felipe R. Blasco; Julie J.H Nati; Anthony P. Farrell (Journal of Fish Biology, 2021)
Intraspecific variation in key traits such as tolerance of warming can have profound effects on ecological and evolutionary processes, notably responses to climate change. The empirical evidence for three primary elements of intraspecific variation in tolerance of warming in fishes is reviewed. The first is purely mechanistic that tolerance varies across life stages and as fishes become mature. The limited evidence indicates strongly that this is the case, possibly because of universal physiological principles. The second is intraspecific variation that is because of phenotypic plasticity, also a mechanistic phenomenon that buffers individuals’ sensitivity to negative impacts of global warming in their lifetime, or to some extent through epigenetic effects over successive generations. Although the evidence for plasticity in tolerance to warming is extensive, more work is required to understand underlying mechanisms and to reveal whether there are general patterns. The third element is intraspecific variation based on heritable genetic differences in tolerance, which underlies local adaptation and may define long‐term adaptability of a species in the face of ongoing global change. There is clear evidence of local adaptation and some evidence of heritability of tolerance to warming, but the knowledge base is limited with detailed information for only a few model or emblematic species. There is also strong evidence of structured variation in tolerance of warming within species, which may have ecological and evolutionary significance irrespective of whether it reflects plasticity or adaptation. Although the overwhelming consensus is that having broader intraspecific variation in tolerance should reduce species vulnerability to impacts of global warming, there are no sufficient data on fishes to provide insights into particular mechanisms by which this may occur.

Advanced materials and technologies for supercapacitors used in energy conversion and storage: a review - M. I. A. Abdel Maksoud; Ramy Amer Fahim; Ahmed Esmail Shalan; M. Abd Elkodous; S. O. Olojede; Ahmed I. Osman; Charlie Farrell; Ala’a H. Al-Muhtaseb; A. S. Awed; A. H. Ashour; David W. Rooney (Environmental Chemistry Letters, 2021)
Supercapacitors are increasingly used for energy conversion and storage systems in sustainable nanotechnologies. Graphite is a conventional electrode utilized in Li-ion-based batteries, yet its specific capacitance of 372 mA h g −1 is not adequate for supercapacitor applications. Interest in supercapacitors is due to their high-energy capacity, storage for a shorter period and longer lifetime. This review compares the following materials used to fabricate supercapacitors: spinel ferrites, e.g., MFe 2 O 4 , MMoO 4 and MCo 2 O 4 where M denotes a transition metal ion; perovskite oxides; transition metals sulfides; carbon materials; and conducting polymers. The application window of perovskite can be controlled by cations in sublattice sites. Cations increase the specific capacitance because cations possess large orbital valence electrons which grow the oxygen vacancies. Electrodes made of transition metal sulfides, e.g., ZnCo 2 S 4 , display a high specific capacitance of 1269 F g −1 , which is four times higher than those of transition metals oxides, e.g., Zn–Co ferrite, of 296 F g −1 . This is explained by the low charge-transfer resistance and the high ion diffusion rate of transition metals sulfides. Composites made of magnetic oxides or transition metal sulfides with conducting polymers or carbon materials have the highest capacitance activity and cyclic stability. This is attributed to oxygen and sulfur active sites which foster electrolyte penetration during cycling, and, in turn, create new active sites.

Historical biogeography of smoothhound sharks (genus Mustelus ) of Southern Africa reveals multiple dispersal events from the Northern Hemisphere - Simo N. Maduna; Kelvin L. Hull; Edward D. Farrell; Jessica J. Boomer; Ana Veríssimo; Ilaria A. M. Marino; Carlotta Mazzoldi; Lorenzo Zane; Sabine P. Wintner; Mikhail V. Chesalin; Charlene da Silva; Chrysoula Gubili; et al. (Systematics and Biodiversity, 2020)

ACMT Position Statement: Medication Administration and Safety During the Response to COVID-19 Pandemic - Brenna M. Farmer; Jon B. Cole; Travis D. Olives; Natalija M. Farrell; Rama Rao; Lewis S. Nelson; Maryann Mazer-Amirshahi; Andrew I. Stolbach (Journal of Medical Toxicology, 2020)

Assessing Chemical Mechanisms Underlying the Effects of Sunflower Pollen on a Gut Pathogen in Bumble Bees - Lynn S. Adler; Alison E. Fowler; Rosemary L. Malfi; Patrick R. Anderson; Lily M. Coppinger; Pheobe M. Deneen; Stephanie Lopez; Rebecca E. Irwin; Iain W. Farrell; Philip C. Stevenson (Journal of Chemical Ecology, 2020)

Horizon scanning for South African biodiversity: A need for social engagement as well as science - Colleen L. Seymour; Lindsey Gillson; Matthew F. Child; Krystal A. Tolley; Jock C. Curie; Jessica M. da Silva; Graham J. Alexander; Pippin Anderson; Colleen T. Downs; Benis N. Egoh; David A. Ehlers Smith; Yvette C. Ehlers Smith; et al. (Ambio, 2020)

Improving Habitat Connectivity in a Typha-Dominated Wetland Shows Increased Larval Northern Pike Survival - Ericka A. Massa; John M. Farrell (Wetlands, 2020)

A Continental-Scale Validation of Ecosystem Service Models - Simon Willcock; Danny A. P. Hooftman; Stefano Balbi; Ryan Blanchard; Terence P. Dawson; Patrick J. O’Farrell; Thomas Hickler; Malcolm D. Hudson; Mats Lindeskog; Javier Martinez-Lopez; Mark Mulligan; Belinda Reyers; et al. (Ecosystems, 2019)

The effect of acute warming and thermal acclimation on maximum heart rate of the common killifish Fundulus heteroclitus - Hamid Safi; Yangfan Zhang; Patricia M. Schulte; Anthony P. Farrell (Journal of Fish Biology, 2019)
Common killifish Fundulus heteroclitus were acclimated to ecologically relevant temperatures (5, 15 and 33°C) and their maximum heart rate ( f Hmax ) was measured at each acclimation temperature during an acute warming protocol. Acclimation to 33°C increased peak f Hmax by up to 32% and allowed the heart to beat rhythmically at a temperature 10°C higher when compared with acclimation to 5°C. Independent of acclimation temperature, peak f Hmax occurred about 3°C cooler than the temperature that first produced cardiac arrhythmias. Thus, when compared with previously published values for the critical thermal maximum of F. heteroclitus , the temperature for peak f Hmax was cooler and the temperature that first produced cardiac arrhythmias was similar to these critical thermal maxima. The considerable thermal plasticity of f Hmax demonstrated in the present study is entirely consistent with eurythermal ecology of killifish, as shown previously for another eurythermal fish Gillichthys mirabilis .

Vegetation Response and Juvenile Northern Pike (Esox lucius) Outmigration Following Connectivity Enhancement of a Typha Dominated Coastal Wetland - Brandeis L. Neveldine; John Paul Leblanc; John M. Farrell (Wetlands, 2019)

Strong genetic isolation despite wide distribution in a commercially exploited coastal shark - Kelvin L. Hull; Tamaryn A. Asbury; Charlene da Silva; Matthew Dicken; Ana Veríssimo; Edward D. Farrell; Stefano Mariani; Carlotta Mazzoldi; Ilaria A. M. Marino; Lorenzo Zane; Simo N. Maduna; Aletta E. Bester-van der Merwe (Hydrobiologia, 2019)

Investigation of round goby viral haemorrhagic septicaemia outbreak in New York - Rodman G. Getchell; Erika J. First; Steven M. Bogdanowicz; Jose A. Andrés; Adam T. Schulman; Jordan Kramer; Geofrey E. Eckerlin; John M. Farrell; Hélène Marquis (Journal of Fish Diseases, 2019)
Eleven viral haemorrhagic septicaemia virus (VHSV) genotype IVb isolates were sequenced, and their genetic variation explored to determine the source of a VHS outbreak on the eastern shore of Cayuga Lake. An active fish kill of round gobies ( Neogobius melanostomus , Pallas) was intensively sampled at King Ferry, NY and nearby Long Point State Park in May 2017. Gross lesions observed on 67 moribund round gobies and two rock bass ( Ambloplites rupestris , Rafinesque) included moderately haemorrhagic internal organs and erythematous areas on the head, flank, and fins. RT‐qPCR tests for VHSV were positive for all 69 fish. Viral isolation on epithelioma papulosum cyprinid cells showed cytopathic effect characteristic of VHSV for six round goby samples from King Ferry. The complete nucleotide sequence of the VHSV IVb genomes of five Cayuga Lake round goby isolates were derived on an Illumina platform along with 2017 VHSV IVb isolates from round gobies collected from the following: Lake Erie near Dunkirk, NY; the St. Lawrence River near Clayton and Cape Vincent, NY; and Lake St. Lawrence near Massena, NY. The phylogenetic tree created from these aligned sequences and four other complete VHSV IVb genomes shows Cayuga Lake isolates are closely related to the Lake Erie isolates.

RGD-decorated cholesterol stabilized polyplexes for targeted siRNA delivery to glioblastoma cells - Bo Lou; Kate Connor; Kieron Sweeney; Ian S. Miller; Alice O’Farrell; Eduardo Ruiz-Hernandez; David M. Murray; Garry P. Duffy; Alan Wolfe; Enrico Mastrobattista; Annette T. Byrne; Wim E. Hennink (Drug Delivery and Translational Research, 2019)

Contrasting latitudinal gradients of body size in helminth parasites and their hosts - Tad Dallas; Alyssa‐Lois M. Gehman; A. Alonso Aguirre; Sarah A. Budischak; John M. Drake; Maxwell J. Farrell; Ria Ghai; Shan Huang; Ignacio Morales‐Castilla (Global Ecology and Biogeography, 2019)
Aim We examined body size scaling relationships for two developmental life stages of parasitic helminths (egg and adult) separately in relationship to latitude (i.e. Bergmann's rule), temperature and temperature seasonality. Given that helminth eggs experience environmental conditions more directly, whereas adults live inside infected host individuals, we predict stronger environmentally driven gradients of body size for eggs than for adults. Location Global. Time period Present day. Major taxa studied Parasitic helminths. Methods We compiled egg size and adult body size data (both minimum and maximum) for 265 parasitic helminth species from the literature, along with species latitudinal distribution information using an extensive global helminth occurrence database. We then examined how the average helminth egg and adult body size of all helminth species present (minimum and maximum separately) scaled with latitude, temperature and temperature variability, using generalized linear models. Results Both the egg size and the adult body size of helminths tended to decrease towards higher latitudes, although we found the opposite body size scaling pattern for their host species. Helminth sizes were also positively correlated with temperature and negatively, but more weakly, with temperature seasonality. Main conclusions Instead of following the body size patterns of their hosts, helminth parasites are more similar to other ectotherms in that they follow the converse Bergmann's rule. This pattern did not differ between helminth developmental stages, suggesting that mean annual temperature and seasonality are unlikely to be related mechanistically to body size variation in this case.

Prey selection by larval northern pike ( Esox lucius ) exposed to different zooplankton assemblages representing seasonally flooded wetland and nearshore bay habitats - Ericka A. Massa; John M. Farrell (Limnology and Oceanography, 2019)
A prey selection experiment was designed to investigate whether northern pike larvae, at swim‐up and advanced stages, select similar zooplankton prey in seasonally flooded wetlands and nearshore littoral zones, which represent primary St. Lawrence River northern pike spawning habitats. At first exogenous feeding, naïve swim‐up larvae exposed to both wetland and nearshore zooplankton were generalist consumers, feeding primarily on cyclopoid copepods and small cladocerans. No positive selection was observed for any prey taxa. Advanced larvae began to exhibit positive selection for large cladocerans. Significantly larger‐sized prey were consumed by advanced larvae given wetland vs. nearshore zooplankton. Large cladocerans made up a greater proportion of the assemblage originating from seasonally flooded wetlands vs. nearshore habitats, and may explain the difference in size selectivity. Our laboratory experiment suggests pike hatched in wetland environments have greater access to preferred, large cladoceran prey, and differences in spatial and temporal spawning distributions may have important implications for zooplankton availability and hence food consumption during the critical larval period.

Modeling the effective spawning and nursery habitats of northern pike within a large spatiotemporally variable river landscape (St. Lawrence River, Canada) - Aline Foubert; Céline Le Pichon; Marc Mingelbier; John M. Farrell; Jean Morin; Frédéric Lecomte (Limnology and Oceanography, 2019)
Spawning and nursery habitats are often spatially disjunct as a consequence of specific life history stage habitat requirements and spatiotemporal habitat changes. Nevertheless, free‐swimming larvae originating from spawning habitats must reach productive nurseries to maximize survival. We examined spawning and nursery habitats of northern pike ( Esox lucius ) over the past 50 yr to investigate how habitat connectivity and hydrological variability interact to alter the distribution of effective spawning habitat. Habitat models coupled to a least‐cost approach were developed to quantify connectivity between habitats in two contrasting regions of the St. Lawrence River (Canada): a riverine corridor lake (~ 46 km) and a large fluvial lake (~ 48 km). Our simulations demonstrate that depending on hydrological conditions, between 3% to 51% of spawning habitat used by adults in the riverine corridor, and 22% to 90% in the lake, allowed larval survival up to the fifth week of development. Although rapid dewatering of spawning habitat is responsible for most spawning losses in the fluvial lake, increasing water currents were responsible for dispersing larvae away from suitable habitats in the riverine corridor. However, stable hydrological conditions led to spatial overlapping of spawning and nursery habitats favoring larval survival and growth. In addition, downstream larval dispersal by low water currents allowed larvae to reach spatially disjunct nursery habitat, especially in the lake. Our results indicate that despite the vast areas of potentially suitable habitats provided by large vegetated floodplains of fluvial lakes, the effective spawning habitats favoring early‐life recruitment are much more heterogeneous and variable both spatially and temporally.

A multi-criterion approach for prioritizing areas in urban ecosystems for active restoration following invasive plant control - Elana Mostert; Mirijam Gaertner; Patricia M. Holmes; Patrick J. O’Farrell; David M. Richardson (Environmental Management, 2018)

Correction to: Managing Urban Plant Invasions: a Multi-Criteria Prioritization Approach - Luke J. Potgieter; Mirijam Gaertner; Ulrike M. Irlich; Patrick J. O’Farrell; Louise Stafford; Hannah Vogt; David M. Richardson (Environmental Management, 2018)

Managing Urban Plant Invasions: a Multi-Criteria Prioritization Approach - Luke J. Potgieter; Mirijam Gaertner; Ulrike M. Irlich; Patrick J. O’Farrell; Louise Stafford; Hannah Vogt; David M. Richardson (Environmental Management, 2018)

Variation in Detrital Resource Stoichiometry Signals Differential Carbon to Nutrient Limitation for Stream Consumers Across Biomes - Kaitlin J. Farrell; Amy D. Rosemond; John S. Kominoski; Sophia M. Bonjour; Janine Rüegg; Lauren E. Koenig; Christina L. Baker; Matt T. Trentman; Tamara K. Harms; William H. McDowell (Ecosystems, 2018)

How the Comprehensive Cancer Control National Partnership shapes the public health workforce - Margaret M. Farrell; Kelsy M. Gibson; Angela Marler; Leslie Given; Aubrey Van Kirk Villalobos; Candace Deaton Maynard; Frank S. Bright; Ginny Thompson Kirklin; Truemenda C. Green; Melanie Ruhe; Julia Thorsness; Stephanie Weiss (Cancer Causes & Control, 2018)

Resolving the ambiguities in the identification of two smooth-hound sharks (Mustelus mustelus and Mustelus punctulatus) using genetics and morphology - I. A. M. Marino; L. Finotto; F. Colloca; M. Di Lorenzo; M. Gristina; E. D. Farrell; L. Zane; C. Mazzoldi (Marine Biodiversity, 2018)

A three‐phase excess post‐exercise oxygen consumption in Atlantic salmon Salmo salar and its response to exercise training - Y. Zhang; G. Claireaux; H. Takle; S. M. Jørgensen; A. P. Farrell (Journal of Fish Biology, 2018)
The recovery of oxygen uptake to the standard metabolic rate (SMR) following exhaustive chasing exercise in Atlantic salmon Salmo salar parr occurred in three phases (rapid, plateau and slow). The initial recovery phase lasted 0·7 h and contributed 16% to the total excess post‐exercise oxygen consumption (EPOC). It was followed by a longer plateau phase that contributed 53% to the total EPOC. The slow recovery phase that completed recovery of SMR, which has not been reported previously, made a 31% contribution to the total EPOC. The plasticity of EPOC was demonstrated in exercise‐trained fish. Exercise training increased EPOC by 39% when compared with control fish (mean ± S.E., 877·7 ± 73·1 v . 629·2 ± 53·4 mg O 2 kg −1 , d.f. = 9, P 0·05), with the duration of the plateau phase increasing by 38% (4·7 ± 0·58 v . 3·4 ± 0·16 h, d.f. = 9, P 0·05) and the contribution of the slow phase to the total EPOC increasing by 80% (173·9 ± 23·9 v . 312·5 ± 50·4 mg O 2 kg −1 , d.f. = 9, P v . 513·6 ± 43·1 mg O 2 kg −1 ; d.f. = 9, P = 0·01). To substantiate the hypothesis that the plateau and slow recovery phase of EPOC was related to general metabolic recovery following exhaustive exercise, the time‐course for recovery of SMR was compared with previously published metabolite recovery profiles. The final phase of metabolic recovery was temporally associated with the final phases of gluconeogenesis, lactate oxidation and muscle intracellular pH regulation. Therefore, the plasticity of the latter phase of EPOC agreed with the known effects of exercise training in fishes.

A lake classification concept for a more accurate global estimate of the dissolved inorganic carbon export from terrestrial ecosystems to inland waters - Fabian Engel; Kaitlin J. Farrell; Ian M. McCullough; Facundo Scordo; Blaize A. Denfeld; Hilary A. Dugan; Elvira de Eyto; Paul C. Hanson; Ryan P. McClure; Peeter Nõges; Tiina Nõges; Elizabeth Ryder; et al. (The Science of Nature, 2018)

The Role of Clinical Pharmacists in the Emergency Department - Brenna M. Farmer; Bryan D. Hayes; Rama Rao; Natalija Farrell; Lewis Nelson (Journal of Medical Toxicology, 2018)

A rainbow trout Oncorhynchus mykiss strain with higher aerobic scope in normoxia also has superior tolerance of hypoxia - Y. Zhang; T. M. Healy; W. Vandersteen; P. M. Schulte; A. P. Farrell (Journal of Fish Biology, 2018)
This study compared parr from three strains of rainbow trout Oncorhynchus mykiss to examine intraspecific variation in metabolic traits, hypoxia tolerance and upper thermal tolerance in this species. At the strain level, variation in absolute aerobic scope (AAS), critical oxygen level (O 2crit ), incipient lethal oxygen saturation (ILOS) and critical thermal maximum (CT max ) generally exhibited consistent differences among the strains, suggesting the possibility of functional associations among these traits. This possibility was further supported at the individual level by a positive correlation between ILOS and O 2crit and a negative correlation between O 2crit and AAS. These results indicate that intraspecific differences in hypoxia tolerance among strains of O. mykiss may be primarily determined by differences in the ability to maintain oxygen uptake in hypoxia and that variation in aerobic scope in normoxia probably plays a role in determining the ability of these fish to sustain metabolism aerobically as water oxygen saturation is reduced.

Adolescent cannabinoid exposure effects on natural reward seeking and learning in rats - H. Schoch; M. Y. Huerta; C. M. Ruiz; M. R. Farrell; K. M. Jung; J. J. Huang; R. R. Campbell; D. Piomelli; S. V. Mahler (Psychopharmacology, 2018)

Next generation sequencing is informing phenotype: a TP53 example - R. O’Shea; R. Clarke; E. Berkley; C. Giffney; M. Farrell; E. O’Donovan; D. J. Gallagher (Familial Cancer, 2018)

Alien plants as mediators of ecosystem services and disservices in urban systems: a global review - Luke J. Potgieter; Mirijam Gaertner; Christoph Kueffer; Brendon M. H. Larson; Stuart W. Livingstone; Patrick J. O’Farrell; David M. Richardson (Biological Invasions, 2017)

Evaluating local adaptation of a complex phenotype: reciprocal tests of pigmy rattlesnake venoms on treefrog prey - Sarah A. Smiley-Walters; Terence M. Farrell; H. Lisle Gibbs (Oecologia, 2017)

Responses of a Federally Endangered Songbird to Understory Thinning in Oak-Juniper Woodlands - Ashley M. Long; Mike E. Marshall; Michael L. Morrison; K. Brian Hays; Shannon L. Farrell (Environmental Management, 2017)

Erratum to: Which environmental factors trigger the dominance of phytoplankton species across a moisture gradient of shallow lakes? - Irina Izaguirre; María Laura Sánchez; M. Romina Schiaffino; Inés O’Farrell; Paula Huber; Nora Ferrer; Josefina Zunino; Leonardo Lagomarsino; Miguel Mancini (Hydrobiologia, 2017)

Aluminum toxicity risk reduction as a result of reduced acid deposition in Adirondack lakes and ponds - Toby M. Michelena; Jeremy L. Farrell; David A. Winkler; Christine A. Goodrich; Charles W. Boylen; James W. Sutherland; Sandra A. Nierzwicki-Bauer (Environmental Monitoring and Assessment, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Seasonal migration of the starry smooth‐hound shark Mustelus asterias as revealed from tag‐recapture data of an angler‐led tagging programme - N. W. P. Brevé; H. V. Winter; H. M. J. Van Overzee; E. D. Farrell; P. A. Walker (Journal of Fish Biology, 2016)
The primary aim of this long‐term angler‐led tagging programme was to gain information about seasonal changes in distribution of the starry smooth‐hound shark Mustelus asterias , along the Dutch coast for management and conservation purposes. Between 2011 and 2014, M. asterias comprised 92·6% ( n = 2418) of the total elasmobranch catch ( n = 2612) by the licenced group of taggers within the Dutch Delta of which 2244 M. asterias were fin‐tagged with plastic rototags. Sex and total length ( L T ) composition inside the eastern tidal basin (Oosterschelde) were significantly different, i.e. more females and larger individuals, than outside indicating a pupping ground, which was confirmed by the capture of 30 newborn pups (≤32 cm). The distribution pattern of reported recaptured M. asterias (return‐rate 3·6%, n = 80) showed a circannual migration between summering in the southern North Sea and wintering in the English Channel and the Bay of Biscay, and suggests that M. asterias is philopatric. The Dutch angling season for M. asterias runs from approximately mid‐May to mid‐October when the water temperature is above 13° C. Recaptures of eight mature females, but no males in the Bay of Biscay, indicate partial spatial segregation by sex, where mature females migrate over larger distances than immature females and males. These observations, with the absence of recaptures in other known summering areas ( i.e. the Irish Sea and Bristol Channel), suggest that the southern North Sea is used by a separate population. Implications for management and recommendations to improve and expand the study approach are discussed.

Biological data from a data‐deficient shark: the Arabian smoothhound Mustelus mosis (Carcharhiniformes: Triakidae) - A. B. M. Moore; A. C. Henderson; E. D. Farrell; L. B. Weekes (Journal of Fish Biology, 2016)
The present study provides information on length distribution, reproductive biology and diet of Mustelus mosis based on individuals caught in waters off the eastern Arabian Peninsula. Although ageing of vertebral centra was attempted, band pairs were of low clarity and counts could not be confidently assigned.

The complete peach dehydrin family: characterization of three recently recognized genes - Carole Leavel Bassett; Kirsten M. Fisher; Robert E. Farrell (Tree Genetics & Genomes, 2015)

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

Network analysis reveals that bacteria and fungi form modules that correlate independently with soil parameters - Alexandre B. de Menezes; Miranda T. Prendergast‐Miller; Alan E. Richardson; Peter Toscas; Mark Farrell; Lynne M. Macdonald; Geoff Baker; Tim Wark; Peter H. Thrall (Environmental Microbiology, 2015)
Summary Network and multivariate statistical analyses were performed to determine interactions between bacterial and fungal community terminal restriction length polymorphisms as well as soil properties in paired woodland and pasture sites. Canonical correspondence analysis ( CCA ) revealed that shifts in woodland community composition correlated with soil dissolved organic carbon, while changes in pasture community composition correlated with moisture, nitrogen and phosphorus. Weighted correlation network analysis detected two distinct microbial modules per land use. Bacterial and fungal ribotypes did not group separately, rather all modules comprised of both bacterial and fungal ribotypes. Woodland modules had a similar fungal : bacterial ribotype ratio, while in the pasture, one module was fungal dominated. There was no correspondence between pasture and woodland modules in their ribotype composition. The modules had different relationships to soil variables, and these contrasts were not detected without the use of network analysis. This study demonstrated that fungi and bacteria, components of the soil microbial communities usually treated as separate functional groups as in a CCA approach, were co‐correlated and formed distinct associations in these adjacent habitats. Understanding these distinct modular associations may shed more light on their niche space in the soil environment, and allow a more realistic description of soil microbial ecology and function.

Which environmental factors trigger the dominance of phytoplankton species across a moisture gradient of shallow lakes? - Irina Izaguirre; María Laura Sánchez; M. Romina Schiaffino; Inés O’Farrell; Paula Huber; Nora Ferrer; Josefina Zunino; Leonardo Lagomarsino; Miguel Mancini (Hydrobiologia, 2015)

Genetic Differentiation in Response to Selection for Water-Soluble Carbohydrate Content in Perennial Ryegrass (Lolium perenne L.) - J. A. Gallagher; L. B. Turner; A. J. Cairns; M. Farrell; J. A. Lovatt; K. Skøt; I. P. Armstead; M. O. Humphreys; I. Roldan-Ruiz (BioEnergy Research, 2015)

Low Concentrations of Contaminants in an Invasive Cyprinid, the Rudd, in a Great Lakes Area of Concern - Kevin L. Kapuscinski; John M. Farrell; Gordon Paterson; Michael A. Wilkinson; Lawrence C. Skinner; Wayne Richter; Anthony J. Gudlewski (Bulletin of Environmental Contamination and Toxicology, 2014)

Plant growth responses to biochar addition: an Australian soils perspective - Lynne M. Macdonald; Mark Farrell; Lukas Van Zwieten; Evelyn S. Krull (Biology and Fertility of Soils, 2014)

Differentiating between the supply of N to wheat from above and belowground residues of preceding crops of pea and canola - Melissa M. Arcand; J. Diane Knight; Richard E. Farrell (Biology and Fertility of Soils, 2014)

Facing warm temperatures during migration: cardiac mRNA responses of two adult Oncorhynchus nerka populations to warming and swimming challenges - K. Anttila; E. J. Eliason; K. H. Kaukinen; K. M. Miller; A. P. Farrell (Journal of Fish Biology, 2014)
The main findings of the current study were that exposing adult sockeye salmon Onchorhynchus nerka to a warm temperature that they regularly encounter during their river migration induced a heat shock response at an mRNA level, and this response was exacerbated with forced swimming. Similar to the heat shock response, increased immune defence‐related responses were also observed after warm temperature treatment and with a swimming challenge in two different populations (Chilko and Nechako), but with some important differences. Microarray analyses revealed that 347 genes were differentially expressed between the cold (12–13° C) and warm (18–19° C) treated fish, with stress response ( GO :0006950) and response to fungus ( GO :0009620) elevated with warm treatment, while expression for genes involved in oxidative phosphorylation ( GO :0006119) and electron transport chain ( GO :0022900) elevated for cold‐treated fish. Analysis of single genes with real‐time quantitative PCR revealed that temperature had the most significant effect on mRNA expression levels, with swimming and population having secondary influences. Warm temperature treatment for the Chilko population induced expression of heat shock protein ( hsp ) 90α , hsp90β and hsp30 as well as interferon‐inducible protein . The Nechako population, which is known to have a narrower thermal tolerance window than the Chilko population, showed even more pronounced stress responses to the warm treatment and there was significant interaction between population and temperature treatment for hsp90β expression. Moreover, significant interactions were noted between temperature treatment and swimming challenge for hsp90α and hsp30 , and while swimming challenge alone increased expression of these hsp s, the expression levels were significantly elevated in warm‐treated fish swum to exhaustion. In conclusion, it seems that adult O. nerka currently encounter conditions that induce several cellular defence mechanisms during their once‐in‐the‐lifetime migration. As river temperatures continue to increase, it remains to be seen whether or not these cellular defences provide sufficient protection for all O. nerka populations.

Nitrogen supply from belowground residues of lentil and wheat to a subsequent wheat crop - Melissa M. Arcand; Reynald Lemke; Richard E. Farrell; J. Diane Knight (Biology and Fertility of Soils, 2014)

Biochar and fertiliser applications influence phosphorus fractionation and wheat yield - Mark Farrell; Lynne M. Macdonald; Greg Butler; Ivan Chirino-Valle; Leo M. Condron (Biology and Fertility of Soils, 2014)

Multivariate analysis of MLH1 c.1664T>C (p.Leu555Pro) mismatch repair gene variant demonstrates its pathogenicity - M. P. Farrell; D. J. Hughes; M. Drost; A. J. Wallace; R. J. Cummins; T. A. Fletcher; M. A. Meany; E. W. Kay; N. de Wind; D. G. Power; E. J. Andrews; A. J. Green; et al. (Familial Cancer, 2013)

Killer cell immunoglobulin-like receptor (KIR) genes and their HLA-C ligands in a Ugandan population - Annettee Nakimuli; Olympe Chazara; Lydia Farrell; Susan E. Hiby; Stephen Tukwasibwe; Olatejumoye Knee; Jyothi Jayaraman; James A. Traherne; Alison M. Elliott; Pontiano Kaleebu; Florence Mirembe; Ashley Moffett (Immunogenetics, 2013)

Estimating belowground nitrogen inputs of pea and canola and their contribution to soil inorganic N pools using 15N labeling - Melissa M. Arcand; J. Diane Knight; Richard E. Farrell (Plant and Soil, 2013)

Low cardiac and aerobic scope in a coastal population of sockeye salmon Oncorhynchus nerka with a short upriver migration - E. J. Eliason; S. M. Wilson; A. P. Farrell; S. J. Cooke; S. G. Hinch (Journal of Fish Biology, 2013)
This study showed that a coastal population (Harrison) of Fraser River sockeye salmon Oncorhynchus nerka had a lower aerobic and cardiac scope compared with interior populations with more challenging upriver spawning migrations, providing additional support to the idea that Fraser River O. nerka populations have adapted physiologically to their local migratory environment.

Comparing community structure on shells of the abalone Haliotis midae and adjacent rock: implications for biodiversity - Zannè Zeeman; George M. Branch; Daniel Farrell; Gavin W. Maneveldt; Deborah Robertson-Andersson; Deena Pillay (Marine Biology, 2013)

Effects of exogenous abscisic acid and gibberellic acid on pre-maturity α-amylase formation in wheat grains - K. R. Kondhare; P. S. Kettlewell; A. D. Farrell; P. Hedden; J. M. Monaghan (Euphytica, 2012)

Feeding patterns and population structure of an invasive cyprinid, the rudd Scardinius erythrophthalmus (Cypriniformes, Cyprinidae), in Buffalo Harbor (Lake Erie) and the upper Niagara River - Kevin L. Kapuscinski; John M. Farrell; Michael A. Wilkinson (Hydrobiologia, 2012)

Clinical correlation and molecular evaluation confirm that the MLH1 p.Arg182Gly (c.544A>G) mutation is pathogenic and causes Lynch syndrome - Michael P. Farrell; David J. Hughes; Ian R. Berry; David J. Gallagher; Emily A. Glogowski; Stewart J. Payne; Michael J. Kennedy; Róisín M. Clarke; Susan A. White; Cian B. Muldoon; Fiona Macdonald; Pauline Rehal; et al. (Familial Cancer, 2012)

Water balance trumps ion balance for early marine survival of juvenile pink salmon (Oncorhynchus gorbuscha) - M. Sackville; J. M. Wilson; A. P. Farrell; C. J. Brauner (Journal of Comparative Physiology B, 2012)

Dead fish swimming: a review of research on the early migration and high premature mortality in adult Fraser River sockeye salmon Oncorhynchus nerka - S. G. Hinch; S. J. Cooke; A. P. Farrell; K. M. Miller; M. Lapointe; D. A. Patterson (Journal of Fish Biology, 2012)
Adult sockeye salmon Oncorhynchus nerka destined for the Fraser River, British Columbia are some of the most economically important populations but changes in the timing of their homeward migration have led to management challenges and conservation concerns. After a directed migration from the open ocean to the coast, this group historically would mill just off shore for 3–6 weeks prior to migrating up the Fraser River. This milling behaviour changed abruptly in 1995 and thereafter, decreasing to only a few days in some years (termed early migration), with dramatic consequences that have necessitated risk‐averse management strategies. Early migrating fish consistently suffer extremely high mortality (exceeding 90% in some years) during freshwater migration and on spawning grounds prior to spawning. This synthesis examines multidisciplinary, collaborative research aimed at understanding what triggers early migration, why it results in high mortality, and how fisheries managers can utilize these scientific results. Tissue analyses from thousands of O. nerka captured along their migration trajectory from ocean to spawning grounds, including hundreds that were tracked with biotelemetry, have revealed that early migrants are more reproductively advanced and ill‐prepared for osmoregulatory transition upon their entry into fresh water. Gene array profiles indicate that many early migrants are also immunocompromised and stressed, carrying a genomic profile consistent with a viral infection. The causes of these physiological changes are still under investigation. Early migration brings O. nerka into the river when it is 3–6° C warmer than historical norms, which for some late‐run populations approaches or exceeds their critical maxima leading to the collapse of metabolic and cardiac scope, and mortality. As peak spawning dates have not changed, the surviving early migrants tend to mill in warm lakes near to spawning areas. These results in the accumulation of many more thermal units and longer exposures to freshwater diseases and parasites compared to fish that delay freshwater entry by milling in the cool ocean environment. Experiments have confirmed that thermally driven processes are a primary cause of mortality for early‐entry migrants. The Fraser River late‐run O. nerka early migration phenomenon illustrates the complex links that exist between salmonid physiology, behaviour and environment and the pivotal role that water temperature can have on population‐specific migration survival.

The effect of adrenaline on the temperature dependency of cardiac action potentials in pink salmon Oncorhynchus gorbuscha - S. Ballesta; L. M. Hanson; A. P. Farrell (Journal of Fish Biology, 2012)
Using sharp electrode impalement, action potentials recorded from atrial and ventricular tissue of pink salmon Oncorhynchus gorbuscha generally decreased in duration with increasing test temperature (6, 10, 16 and 20° C). Stimulation of the tissue using 500 nM adrenaline had no significant effect on the duration of the atrial action potential at any test temperature but lengthened the ventricular action potential by ∼17%.

Antitumor bifunctional dinuclear PtII complex BBR3535 forms interduplex DNA cross-links under molecular crowding conditions - Tereza Muchova; Susana M. Quintal; Nicholas P. Farrell; Viktor Brabec; Jana Kasparkova (JBIC Journal of Biological Inorganic Chemistry, 2012)

Using maximum heart rate as a rapid screening tool to determine optimum temperature for aerobic scope in Pacific salmon Oncorhynchus spp. - M. T. Casselman; K. Anttila; A. P. Farrell (Journal of Fish Biology, 2012)
The mean ± s.e. optimum temperature ( T opt ) for aerobic scope in juvenile coho salmon Oncorhynchus kisutch was determined to be 17·0 ± 0·7° C. The repeated measures protocol took 3 weeks to complete the T opt determination using 12 fish tested at five temperatures separated by 2° C increments. This experiment also demonstrated that the T opt was associated with maximum heart rate ( f H ) failing to maintain a Q 10 ‐related increase with temperature. When maximum f H was produced in anaesthetized fish with pharmacological stimulation and f H measured from electrocardiogram recordings during acute warming, the Arrhenius break temperature (ABT) for Q 10 discontinuities in maximum f H (mean ± s.e . = 17·1 ± 0·5° C for 15 ppm clove oil and 16·5 ± 0·2° C for 50 ppm MS‐222) was statistically indistinguishable from the T opt measured using aerobic scope. Such a determination took only 3 days rather than 3 weeks. Therefore, it is proposed that determining ABT for discontinuities in maximum f H in anaesthetized fish presents itself as a valuable, high‐throughput screening tool to assess T opt in fishes, a metric that has become recognized as being extremely valuable in fish biology and fisheries management.

High-resolution array CGH defines critical regions and candidate genes for microcephaly, abnormalities of the corpus callosum, and seizure phenotypes in patients with microdeletions of 1q43q44 - Blake C. Ballif; Jill A. Rosenfeld; Ryan Traylor; Aaron Theisen; Patricia I. Bader; Roger L. Ladda; Susan L. Sell; Michelle Steinraths; Urvashi Surti; Marianne McGuire; Shelley Williams; Sandra A. Farrell; et al. (Human Genetics, 2012)

A radical approach to beating hypoxia: depressed free radical release from heart fibres of the hypoxia-tolerant epaulette shark (Hemiscyllum ocellatum) - Anthony J. R. Hickey; Gillian M. C. Renshaw; Ben Speers-Roesch; Jeffrey G. Richards; Yuxiang Wang; Anthony P. Farrell; Colin J. Brauner (Journal of Comparative Physiology B, 2012)

Physiological and molecular endocrine changes in maturing wild sockeye salmon, Oncorhynchus nerka, during ocean and river migration - A.-M. Flores; J. M. Shrimpton; D. A. Patterson; J. A. Hills; S. J. Cooke; T. Yada; S. Moriyama; S. G. Hinch; A. P. Farrell (Journal of Comparative Physiology B, 2012)

Introduced and indigenous fungi of the Ross Island historic huts and pristine areas of Antarctica - R. L. Farrell; B. E. Arenz; S. M. Duncan; B. W. Held; J. A. Jurgens; R. A. Blanchette (Polar Biology, 2011)

The efficacy of field techniques for obtaining and storing blood samples from fishes - T. D. Clark; M. R. Donaldson; S. M. Drenner; S. G. Hinch; D. A. Patterson; J. Hills; V. Ives; J. J. Carter; S. J. Cooke; A. P. Farrell (Journal of Fish Biology, 2011)
Prompted by the dramatic increase in the use of blood analyses in fisheries research and monitoring, this study investigated the efficacy of common field techniques for sampling and storing blood from fishes. Three questions were addressed: (1) Do blood samples taken via rapid caudal puncture (the ‘grab‐and‐stab’ technique) yield similar results for live v. sacrificed groups of fishes? (2) Do rapidly obtained caudal blood samples accurately represent blood properties of fishes prior to capture? (3) Does storage of whole blood in an ice slurry for a working day (8·5 h) modify the properties of the plasma? It was shown that haematocrit, plasma ions, metabolites, stress hormones and sex hormones of caudal blood samples were statistically similar when taken from live v. recently sacrificed groups of adult coho salmon Oncorhynchus kisutch . Moreover, this study confirmed by using paired blood samples from cannulated O. kisutch that blood acquired through the caudal puncture technique (mean ± s.e . 142 ± 26 s after capture) was representative of fish prior to capture. Long‐term (8·5 h) cold storage of sockeye salmon Oncorhynchus nerka whole blood caused significant decreases in plasma potassium and chloride, and a significant increase in plasma glucose. Previous research has suggested that these changes largely result from net movements of ions and molecules between the plasma and erythrocytes, movements that can occur within minutes of storage. Thus, blood samples from fishes should be centrifuged as quickly as practicable in the field for separation of plasma and erythrocytes to prevent potentially misleading data.

Testing water-soluble carbohydrate QTL effects in perennial ryegrass (Lolium perenne L.) by marker selection - L. B. Turner; M. Farrell; M. O. Humphreys; O. Dolstra (Theoretical and Applied Genetics, 2010)

Reproductive biology of the starry smooth‐hound shark Mustelus asterias : geographic variation and implications for sustainable exploitation - E. D. Farrell; S. Mariani; M. W. Clarke (Journal of Fish Biology, 2010)
Examination of the reproductive biology of Mustelus asterias in the north‐east Atlantic Ocean highlighted apparent geographical variation in maturity, fecundity and ovarian cycle between Atlantic and Mediterranean populations. The stretch total length ( L ST ) and age at 50% maturity for Atlantic males and females were estimated at 78 cm L ST and 4–5 years and 87 cm L ST and 6 years, respectively. Size at maturity of females was considerably smaller than in Mediterranean specimens (96 cm L ST ). Ovarian fecundity ranged from eight to 27 oocytes and uterine fecundity from six to 18 embryos. The gestation period was c. 12 months, followed by a resting period of c. 12 months, resulting in a biennial cycle. Females stored sperm in the oviducal gland and, unlike Mediterranean specimens, no uterine compartments were observed in Atlantic specimens. This study reveals the existence of strong, possibly adaptive, divergence in life‐history traits in an elasmobranch, whose northern populations may be more susceptible to overexploitation than previously believed.

Early life stage salinity tolerance of wild and hatchery‐reared juvenile pink salmon Oncorhynchus gorbuscha - A. M. Grant; M. Gardner; L. M. Hanson; A. P. Farrell; C. J. Brauner (Journal of Fish Biology, 2010)
Salinity tolerance in wild (Glendale) and hatchery (Quinsam) pink salmon Oncorhynchus gorbuscha (average mass 0·2 g) was assessed by measuring whole body [Na + ] and [Cl − ] after 24 or 72 h exposures to fresh water (FW) and 33, 66 or 100% sea water (SW). Gill Na + , K + ‐ATPase activity was measured following exposure to FW and 100% SW and increased significantly in both populations after a 24 h exposure to 100% SW. Whole body [Na + ] and whole body [Cl − ] increased significantly in both populations after 24 h in 33, 66 and 100% SW, where whole body [Cl − ] differed significantly between Quinsam and Glendale populations. Extending the seawater exposure to 72 h resulted in no further increases in whole body [Na + ] and whole body [Cl − ] at any salinity, but there was more variability among the responses of the two populations. Per cent whole body water ( c. 81%) was maintained in all groups of fish regardless of salinity exposure or population, indicating that the increase in whole body ion levels may have been related to maintaining water balance as no mortality was observed in this study. Thus, both wild and hatchery juvenile O. gorbuscha tolerated abrupt salinity changes, which triggered an increase in gill Na + , K + ‐ATPase within 24 h. These results are discussed in terms of the preparedness of emerging O. gorbuscha for the marine phase of their life cycle.

Holocene Vegetation Dynamics of an Upper St. Lawrence River Wetland: Paleoecological Evidence for a Recent Increase in Cattail (Typha) - Molly Beland Rippke; Matthew T. Distler; John M. Farrell (Wetlands, 2010)

Conservation Planning as a Transdisciplinary Process - BELINDA REYERS; DIRK J. ROUX; RICHARD M. COWLING; AIMEE E. GINSBURG; JEANNE L. NEL; PATRICK O’ FARRELL (Conservation Biology, 2010)
Despite substantial growth in the field of conservation planning, the speed and success with which conservation plans are converted into conservation action remains limited. This gap between science and action extends beyond conservation planning into many other applied sciences and has been linked to complexity of current societal problems, compartmentalization of knowledge and management sectors, and limited collaboration between scientists and decision makers. Transdisciplinary approaches have been proposed as a possible way to address these challenges and to bridge the gap between science and action. These approaches move beyond the bridging of disciplines to an approach in which science becomes a social process resolving problems through the participation and mutual learning of stakeholders. We explored the principles of transdisciplinarity, in light of our experiences as conservation‐planning researchers working in South Africa, to better understand what is required to make conservation planning transdisciplinary and therefore more effective. Using the transdisciplinary hierarchy of knowledge (empirical, pragmatic, normative, and purposive), we found that conservation planning has succeeded in integrating many empirical disciplines into the pragmatic stakeholder‐engaged process of strategy development and implementation. Nevertheless, challenges remain in engagement of the social sciences and in understanding the social context of implementation. Farther up this knowledge hierarchy, at the normative and purposive levels, we found that a lack of integrated land‐use planning and policies (normative) and the dominant effect of national values (purposive) that prioritize growth and development limit the effectiveness and relevance of conservation plans. The transdisciplinary hierarchy of knowledge highlighted that we need to move beyond bridging the empirical and pragmatic disciplines into the complex normative world of laws, policies, and planning and become engaged in the purposive processes of decision making, behavior change, and value transfer. Although there are indications of progress in this direction, working at the normative and purposive levels requires time, leadership, resources, skills that are absent in conservation training and practice, and new forms of recognition in systems of scientific reward and funding.

Safeguarding Biodiversity and Ecosystem Services in the Little Karoo, South Africa - BENIS N. EGOH; BELINDA REYERS; JOSIE CARWARDINE; MICHAEL BODE; PATRICK J. O'FARRELL; KERRIE A. WILSON; HUGH P. POSSINGHAM; MATHIEU ROUGET; WILLEM De LANGE; DAVID M. RICHARDSON; RICHARD M. COWLING (Conservation Biology, 2010)
Global declines in biodiversity and the widespread degradation of ecosystem services have led to urgent calls to safeguard both. Responses to this urgency include calls to integrate the needs of ecosystem services and biodiversity into the design of conservation interventions. The benefits of such integration are purported to include improvements in the justification and resources available for these interventions. Nevertheless, additional costs and potential trade‐offs remain poorly understood in the design of interventions that seek to conserve biodiversity and ecosystem services. We sought to investigate the synergies and trade‐offs in safeguarding ecosystem services and biodiversity in South Africa's Little Karoo. We used data on three ecosystem services—carbon storage, water recharge, and fodder provision—and data on biodiversity to examine several conservation planning scenarios. First, we investigated the amount of each ecosystem service captured incidentally by a conservation plan to meet targets for biodiversity only while minimizing opportunity costs. We then examined the costs of adding targets for ecosystem services into this conservation plan. Finally, we explored trade‐offs between biodiversity and ecosystem service targets at a fixed cost. At least 30% of each ecosystem service was captured incidentally when all of biodiversity targets were met. By including data on ecosystem services, we increased the amount of services captured by at least 20% for all three services without additional costs. When biodiversity targets were reduced by 8%, an extra 40% of fodder provision and water recharge were obtained and 58% of carbon could be captured for the same cost. The opportunity cost (in terms of forgone production) of safeguarding 100% of the biodiversity targets was about US$500 million. Our results showed that with a small decrease in biodiversity target achievement, substantial gains for the conservation of ecosystem services can be achieved within our biodiversity priority areas for no extra cost.

From the Great Lakes flows a Great River: overview of the St. Lawrence River ecology supplement - Jérôme Marty; Michael R. Twiss; Jeffrey J. Ridal; Yves de Lafontaine; John M. Farrell (Hydrobiologia, 2010)

Zooplankton response to shading effects of free-floating plants in shallow warm temperate lakes: a field mesocosm experiment - M. S. Fontanarrosa; G. Chaparro; P. de Tezanos Pinto; P. Rodriguez; I. O’Farrell (Hydrobiologia, 2010)

Water-level regulation and coastal wetland vegetation in the upper St. Lawrence River: inferences from historical aerial imagery, seed banks, and Typha dynamics - John M. Farrell; Brent A. Murry; Donald J. Leopold; Alison Halpern; Molly Beland Rippke; Kevin S. Godwin; Sasha D. Hafner (Hydrobiologia, 2010)

Recent ecological trends in lower trophic levels of the international section of the St. Lawrence River: a comparison of the 1970s to the 2000s - J. M. Farrell; K. T. Holeck; E. L. Mills; C. E. Hoffman; V. J. Patil (Hydrobiologia, 2010)

Tensile Strain as a Regulator of Mesenchymal Stem Cell Osteogenesis - E. M. Kearney; E. Farrell; P. J. Prendergast; V. A. Campbell (Annals of Biomedical Engineering, 2010)

Muskrat Abundance Responses to Water level Regulation Within Freshwater Coastal Wetlands - Jason Toner; John M. Farrell; Jerry V. Mead (Wetlands, 2010)

Erratum to: Distribution of killer cell immunoglobulin-like receptors(KIR) and their HLA-C ligands in two Iranian populations - Susan E. Hiby; Maziar Ashrafian-Bonab; Lydia Farrell; Richard M. Single; Francois Balloux; Mary Carrington; Ashley Moffett; Zahra Ebrahimi (Immunogenetics, 2010)

Distribution of killer cell immunoglobulin-like receptors (KIR) and their HLA-C ligands in two Iranian populations - Susan E. Hiby; Maziar Ashrafian-Bonab; Lydia Farrell; Richard M. Single; Francois Balloux; Mary Carrington; Ashley Moffett (Immunogenetics, 2010)

Swimming performance and associated ionic disturbance of juvenile pink salmon Oncorhynchus gorbuscha determined using different acceleration profiles - L. Nendick; A. Grant; M. Gardner; M. Sackville; C. J. Brauner; A. P. Farrell (Journal of Fish Biology, 2009)
Swimming performance was assessed in juvenile pink salmon Oncorhynchus gorbuscha (body mass −2 ) and a repeated ramped‐critical swimming speed test. Regardless of the swim protocol, the final swimming speeds did not differ significantly ( P > 0·05) among swim tests and ranged from 4·54 to 5·20 body lengths s −1 . This result supports the hypothesis that at an early life stage, O. gorbuscha display the same fatigue speeds independent of the swimming test utilized. Whole body and plasma [Na + ] and [Cl − ] measured at the conclusion of these tests were significantly elevated when compared with control values ( P 0·05) and appear to be predominantly associated with dehydration rather than net ion gain. Given this finding for a small salmonid, estimates of swim performance can be accurately measured with acceleration tests lasting

Laboratory and pilot testing of electrocoagulation for removing scale-forming species from industrial process waters - M. C. Schulz; J. C. Baygents; J. Farrell (International Journal of Environmental Science and Technology, 2009)

Assessment of habitat and predator effects on dwarf rockfishes (Sebastes spp.) using multi model inference - Michael R. O’Farrell; Mary M. Yoklavich; Milton S. Love (Environmental Biology of Fishes, 2009)

Rapid transcriptional response of apple to fire blight disease revealed by cDNA suppression subtractive hybridization analysis - John L. Norelli; Robert E. Farrell; Carole L. Bassett; Angela M. Baldo; Donna A. Lalli; Herb S. Aldwinckle; Michael E. Wisniewski (Tree Genetics & Genomes, 2009)

Reproduction in an invasive exotic catfish Pterygoplichthys disjunctivus in Volusia Blue Spring, Florida, U.S.A. - M. A. Gibbs; J. H. Shields; D. W. Lock; K. M. Talmadge; T. M. Farrell (Journal of Fish Biology, 2008)
Morphology and reproductive strategies of a population of invasive loricariid catfish, Pterygoplichthys disjunctivus , in Volusia Blue Spring, Florida, were examined using morphological characters, gonado‐somatic indices and batch fecundity. This species has cystovarian ovaries, a left ovary that is significantly larger than the right ovary, and is highly fecund. Ovaries contained multiple oocyte size classes and completely spent females were not found, both of which indicate that this species is a multiple spawner. Reproductive patterns changed significantly between the first (2005) and the last (2007) years of this study; female fish became capable of spawning at a smaller size, a greater proportion of the captured population were capable of spawning each year and female batch fecundity increased, as did male and female gonado‐somatic indices. Plasticity of P. disjunctivus reproductive patterns is discussed in relation to resource availability and environmental stability.

The effect of egg size and nutrient content on larval performance: implications to protracted spawning in northern pike (Esox lucius Linnaeus) - Brent A. Murry; John M. Farrell; Kimberly L. Schulz; Mark A. Teece (Hydrobiologia, 2008)

Potential effects of spawning habitat changes on the segregation of northern pike (Esox lucius) and muskellunge (E. masquinongy) in the Upper St. Lawrence River - John E. Cooper; Jerry V. Mead; John M. Farrell; Robert G. Werner (Hydrobiologia, 2008)

Current and future directions for pike ecology and management: a summary and synthesis - P. Anders Nilsson; Christian Skov; John M. Farrell (Hydrobiologia, 2008)

Preface to the International Pike Symposium: merging knowledge of ecology, biology, and management for a circumpolar species - John M. Farrell; Christian Skov; Anders Nilsson (Hydrobiologia, 2008)

Air breathing minimizes post‐exercise lactate load in the tropical Pacific tarpon, Megalops cyprinoides Broussonet 1782 but oxygen debt is repaid by aquatic breathing - R. M. G. Wells; J. Baldwin; R. S. Seymour; K. A. Christian; A. P. Farrell (Journal of Fish Biology, 2007)
Swimming in a flume at reduced water pO 2 resulted in muscle and blood lactate levels in Pacific tarpon Megalops cyprinoides that were significantly higher when fish did not have access to air. Blood glucose and haematological variables were unchanged throughout the regimes of exercise at two swimming speeds and hypoxia. Strenuous exercise with bouts of burst swimming, however, resulted in both high blood lactate and glucose, and perturbed haematological status with elevated haemoglobin and reduced mean cell‐haemoglobin concentration. Post‐exercise recovery was achieved through aquatic breathing rather than by air breathing. The air‐breathing organ in Pacific tarpon therefore prolonged aerobic activity, but gill breathing was used to repay oxygen debt.

The hypoxic threshold for maximum cardiac performance in rainbow trout Oncorhynchus mykiss (Walbaum) during simulated exercise conditions at 18° C - L. M. Hanson; A. P. Farrell (Journal of Fish Biology, 2007)
Perfused rainbow trout Oncorhynchus mykiss hearts exposed to simulated exercise conditions (hypoxia, hyperkalemia and acidosis) at 18° C experienced complete failure of maximum cardiac performance at oxygen tensions P

Continuous measurement of oxygen tensions in the air-breathing organ of Pacific tarpon (Megalops cyprinoides) in relation to aquatic hypoxia and exercise - Roger S. Seymour; Anthony P. Farrell; Keith Christian; Timothy D. Clark; Michael B. Bennett; Rufus M. G. Wells; John Baldwin (Journal of Comparative Physiology B, 2007)

Quantification of native muskellunge nursery habitat: influence of body size, fish community composition, and vegetation structure - Brent A. Murry; John M. Farrell (Environmental Biology of Fishes, 2007)

Development, implementation, and evaluation of an international muskellunge management strategy for the upper St Lawrence River - John M. Farrell; Rodger M. Klindt; John M. Casselman; Steven R. LaPan; Robert G. Werner; Albert Schiavone (Environmental Biology of Fishes, 2007)

Endoglucanase‐producing fungi isolated from Cape Evans historic expedition hut on Ross Island, Antarctica - Shona M. Duncan; Roberta L. Farrell; Joanne M. Thwaites; Benjamin W. Held; Brett E. Arenz; Joel A. Jurgens; Robert A. Blanchette (Environmental Microbiology, 2006)
Summary Early explorers of Antarctica’s Heroic Era erected wooden buildings and brought large quantities of supplies to survive in Antarctica. The introduction of wood and other organic materials provided nutrient sources for fungi that were indigenous to Antarctica or were brought in with the materials and adapted to the harsh conditions. Seventy‐two isolates of filamentous fungi were cultured on selective media from interior structural wood of the Cape Evans historic hut and 27 of these screened positive for the ability to degrade carboxymethyl cellulose (CMC). Four non‐CMC‐degrading isolates were added to a group of 14 CMC‐degrading isolates for further study, and endo‐1, 4‐β‐glucanase activity was demonstrated in the extracellular supernatant from all of these 18 isolates when grown at 4°C, and also when they were grown at 15°C. Isolates of Penicillium roquefortii and Cadophora malorum showed preference for growth at 15°C rather than 25°C or 4°C indicating psychrotrophic characteristics. These results demonstrate that cellulolytic filamentous fungi found in Antarctica are capable of growth at cold temperatures and possess the ability to produce extracellular endo‐1, 4‐β‐glucanase when cultured at cold and temperate temperatures.

Short-Term Ecological Implications of the Diversion of a Highly Polluted Lowland River: A Case Study - N. I. Maidana; I. O’Farrell; R. J. Lombardo; M. dos Santos Afonso (Bulletin of Environmental Contamination and Toxicology, 2005)

Acute Didecyl Dimethyl Ammonium Chloride Toxicity to Larval Lake Sturgeon, Acipenser fulvescens Rafinesque, Walleye Sander vitreus Mitchill, and Northern Pike, Esox lucius Linnaeus - M. A. Gray; S. J. Peake; A. P. Farrell; R. Bruch (Bulletin of Environmental Contamination and Toxicology, 2005)

Coupling non‐invasive physiological assessments with telemetry to understand inter‐individual variation in behaviour and survivorship of sockeye salmon: development and validation of a technique - S. J. Cooke; G. T. Crossin; D. A. Patterson; K. K. English; S. G. Hinch; J. L. Young; R. F. Alexander; M. C. Healey; G. Van Der Kraak; A. P. Farrell (Journal of Fish Biology, 2005)
Approximately 200 km from the mouth of the Fraser River, British Columbia, Canada, adult sockeye salmon Oncorhynchus nerka , were gastrically implanted with radio transmitters without anaesthetic. Subsets of the transmitter implanted fish were also biopsied which included drawing blood from the caudal peduncle (3 ml), removal of gill tissue (0·03 g) and quantification of energetic status using a microwave fat meter. Several experiments were used to test the hypothesis that the biopsy had a negligible effect on the subsequent survival and migratory behaviour of transmitter implanted fish. In the first experiment, no difference was found in the survival (both 100%) or tag retention (both 100%) between the two treatment groups (transmitter implanted with and without biopsy) when fish were held in pens for 24 h in the marine environment. Similarly, in other experiments where fish were released to the ocean to resume their migratory journey, no statistical differences were found in the travel times of fish in the two treatment groups, or in the proportion of fish that passed in‐river telemetry checkpoints. These results indicated that the handling and biopsy methods produced similar levels of mortality and tag retention as the telemetry treatment alone and that any changes in behaviour between the two treatment groups did not adversely affect migration time. Based upon the evidence provided from the biotelemetry of >300 adult sockeye salmon, it was felt that this general type of approach could be applicable to other fish species.

Survey of potential sapstain fungi on Pinus radiata in New Zealand - Joanne M. Thwaites; Roberta L. Farrell; Shona M. Duncan; Stephan D. Reay; Robert A. Blanchette; Esther Hadar; Yitzhak Hadar; Thomas C. Harrington; Douglas McNew (New Zealand Journal of Botany, 2005)
A nationwide survey of New Zealand sapstain fungi on Pinus radiata was undertaken between 1996 and 1998 with collections of 1958 samples of material from 869 sites in the North and South Islands. Material was collected from mills, ports, forest plantations of native, exotic, or P. radiata , nurseries, farms, and urban areas. Material collected included branches, twigs, needles or leaves, cones, logs, wood chips, timber, and veneer. From these collections, 2154 potential sapstain fungi, representing 14 known species plus a number of unidentified species, were isolated. The predominant sapstain fungi isolated were Sphaeropsis sapinea, Ophiostoma ips, O. floccosum, O. piliferum, Leptographium procerum , and O. querci. S. sapinea was isolated from all material sampled including collections from the forest floor (including branches, twigs, needles, leaves, cones, and logs) as well as from logs and timber. In contrast Ophiostoma species were mainly found on logs, timber, and wood chips.

Energetics and morphology of sockeye salmon: effects of upriver migratory distance and elevation - G. T. Crossin; S. G. Hinch; A. P. Farrell; D. A. Higgs; A. G. Lotto; J. D. Oakes; M. C. Healey (Journal of Fish Biology, 2004)
Depending on population, wild Fraser River sockeye salmon Oncorhynchus nerka travel distances of 1100 km and ascend elevations ranging from near sea‐level to 1200 m to reach spawning areas. Populations embarking on distant, high elevation migrations ( i.e . Early Stuart, Chilko and Horsefly populations) began their upriver spawning migrations with higher densities of somatic energy ( c . 9·2 to 9·8 MJ kg −1 ) and fewer eggs ( c . 3200 to 3800) than populations making shorter, low elevation migrations ( i.e . Weaver and Adams; c . 7·1 to 8·3 MJ kg −1 gross somatic energy and c . 4300 to 4700 eggs). Populations making difficult upriver migrations also had morphologies that were smaller and more fusiform than populations making less difficult migrations, traits that may facilitate somatic energy conservation by reducing transport costs. Indeed, fish travelling long distances expended less somatic energy per unit of migratory difficulty than those travelling shorter distances (2·8 to 3·8 kJ v . 10–1400 kJ). Consistent with evolutionary theory, difficult migrations appear to select for energy efficiency but ultimately fish making more difficult migrations produce fewer eggs, even when differences in body length have been accounted for. Despite large among‐population differences in somatic energy at the start of upriver migration, all populations completed migration and spawning, and subsequently died, with c . 4 MJ kg −1 of energy remaining, a level which may reflect a threshold to sustain life.

The effect of temperature and acclimation period on repeat swimming performance in cutthroat trout - M. J. MacNutt; S. G. Hinch; A. P. Farrell; S. Topp (Journal of Fish Biology, 2004)
Hatchery cutthroat trout Oncorhynchus clarki clarki were used to examine the effects of 48 h and 3 week temperature acclimation periods on critical swimming speed ( U crit ). The U crit was determined for fish at acclimation temperatures of 7, 14 and 18° C using two consecutive ramp‐ U crit tests in mobile Brett‐type swim tunnels. An additional group was tested at the stock's ambient rearing temperature of 10° C. The length of the temperature acclimation period had no significant effect on either the first or the second U crit ( U crit‐1 and U crit‐2 , respectively) or on the recovery ratio (the quotient of U crit‐2 U crit‐1 −1 ). As anticipated, there was a significant positive relationship between U crit‐1 and temperature ( P U crit‐2 and temperature ( P = 0·10). Acclimation temperature had no significant effect ( P = 0·71) on the recovery ratio. These results indicate that a 48 h acclimation to experimental temperatures within the range of −3 to +8° C of the acclimation temperature may be sufficient in studies of swimming performance with this species. This ability to acclimate rapidly is probably adaptive for cutthroat trout and other species that occupy thermally variable environments.

Multiple transcripts of a gene for a leucine-rich repeat receptor kinase from morning glory (Ipomoea nil) originate from different TATA boxes in a tissue-specific manner - C. L. Bassett; M. L. Nickerson; R. E. Farrell; M. Harrison (Molecular Genetics and Genomics, 2004)

The effect of exercise and captivity on energy partitioning, reproductive maturation and fertilization success in adult sockeye salmon - D. A. Patterson; J. S. Macdonald; S. G. Hinch; M. C. Healey; A. P. Farrell (Journal of Fish Biology, 2004)
Releasing a population of adult Fraser River sockeye salmon Oncorhynchus nerka from an energetically more expensive non‐feeding natural migration (1089 km, natal groups) and allowing them to sexually mature in either a moderate flow (captive exercise group) or a no flow (captive non‐exercise group) environment resulted in significant differences in body energy densities (MJ kg −1 ) among groups (ranked: initial natural migrator > non‐exercise > exercise > natal arrivals). Similarly, per cent body lipids were significantly lower in exercise females compared with non‐exercise females, experimentally confirming the central role lipid catabolism has in powering swimming. Although restricting exercise did result in greater body energy reserves at spawning, this did not result in a reallocation of energy to reproduction, as fecundity, egg size and gonad composition were unchanged among the groups. Furthermore, non‐exercise females had delayed maturity, lower egg deposition rates, and were more likely to die prior to egg ovulation than exercise females and natal spawners. Eggs from captive exercise adult females were more likely to survive to the eyed stage than eggs from captive non‐exercise females, but both captive groups had significantly lower egg fertilization success than natal spawners suggesting that confinement stress played a role in some of results presented. There were no significant differences in plasma levels of glucose, lactate, cortisol and reproductive hormones among the groups, but correlations among acute and chronic indicators of stress were significant among individuals. These results indicate that exercise during the late stages of maturation, as might occur normally, may be required for optimizing reproductive maturation and maximizing reproductive success.

Synteny between a major heading-date QTL in perennial ryegrass (Lolium perenne L.) and the Hd3 heading-date locus in rice - I. P. Armstead; L. B. Turner; M. Farrell; L. Skøt; P. Gomez; T. Montoya; I. S. Donnison; I. P. King; M. O. Humphreys (Theoretical and Applied Genetics, 2004)

SU11248 inhibits tumor growth and CSF-1R-dependent osteolysis in an experimental breast cancer bone metastasis model - Lesley J. Murray; Tinya J. Abrams; Kelly R. Long; Theresa J. Ngai; Lisa M. Olson; Weiru Hong; Paul K. Keast; Jacqueline A. Brassard; Anne Marie O'Farrell; Julie M. Cherrington; Nancy K. Pryer (Clinical & Experimental Metastasis, 2003)

Green‐fluorescent proteins in Caribbean corals - Charles H. Mazel; Michael P. Lesser; Maxim Y. Gorbunov; Thomas M. Barry; Julianne H. Farrell; Kevin D. Wyman; Paul G. Falkowski (Limnology and Oceanography, 2003)
Fluorescent pigments in several Indo‐Pacific and Caribbean anthozoans have recently been identified as proteins related to the Green‐fluorescent protein (GFP) of the hydromedusa Aequorea victoria . Here we show that GFP is widely distributed in many Caribbean species. The fluorescence excitation and emission spectra for the pigment are similar to those reported elsewhere for coral and noncoral GFP and the fluorescence quantum yield is estimated to be 35%. Spectral and molecular characterization of the isolated protein clearly show it to be GFP, and laboratory and in situ fluorescence measurements and Western blot analysis show that it is widespread. Bathymetric studies of GFP content using Western blots for the ecologically important congeneric corals Montastraea faveolata and Montastraea cavernosa show that there is no significant correlation between depth and GFP concentration. Nucleotide sequence data of GFP from M. faveolata and M. cavernosa show 88.2% sequence homology with each other and 46.4% homology with A. victoria GFP, whereas the percent homology with A. victoria at the amino acid level was 31.1 and 28.4% for M. cavernosa and M. faveolata , respectively, and 82.7% with each other. Measurements of reflectance and of the excitation spectrum for chlorophyll fluorescence in GFP‐containing corals indicate that GFP absorption, emission, and reflection have negligible impact on the level of solar radiation reaching the zooxanthellae and therefore play no role in coral photosynthesis by either addition or removal of photons.

Field‐based measurements of oxygen uptake and swimming performance with adult Pacific salmon using a mobile respirometer swim tunnel - A. P. Farrell; C. G. Lee; K. Tierney; A. Hodaly; S. Clutterham; M. Healey; S. Hinch; A. Lotto (Journal of Fish Biology, 2003)
Novel field measurements of critical swimming speed ( U crit ) and oxygen uptake ( M o 2 ) in three species of adult Pacific salmon Oncorhynchus spp. up to 3·5 kg in body mass were made using two newly designed, mobile Brett‐type swim tunnel respirometers sited at a number of field locations in British Columbia, Canada. Measurements of U crit , which ranged from 1· 68 to 2·17 body lengths s −1 , and maximum M o 2 , which ranged from 8·74 to 12·63 mg O 2 kg −1 min −1 depending on the species and field location, were judged to be of similar quality when compared with available data for laboratory‐based studies. Therefore high quality respirometry studies were possible in the field using adult wild swimming salmonids. In addition, the recovery of wild adult Pacific salmon from the exhaustive U crit swim test was sufficiently rapid that swimming performance could be repeated with M o 2 being reestablished. This result suggests that wild adult salmon are capable of carrying a moderate excess post‐exercise oxygen consumption without adversely affecting U crit , maximum M o 2 or swimming economy. Such capabilities may be extremely important for timely migratory passages when salmonids face repetitive hydraulic challenges on their upstream migration.

Swimming patterns and behaviour of upriver-migrating adult pink (Oncorhynchus gorbuscha) and sockeye (O. nerka) salmon as assessed by EMG telemetry in the Fraser River, British Columbia, Canada - Scott G. Hinch; Emily M. Standen; Michael C. Healey; Anthony P. Farrell (Hydrobiologia, 2002)

In vitro cardiac performance in triploid brown trout at two acclimation temperatures - C. Mercier; M. Axelsson; N. Imbert; G. Claireaux; C. Lefrançois; J. Altimiras; A. P. Farrell (Journal of Fish Biology, 2002)
The maximum values for heart rate ( f H ), stroke volume ( V H ), cardiac output ( Q ) and myocardial power output, measured in vitro with a perfused heart preparation, as well as the isometric force‐frequency relationship for atrial and ventricular muscle strips, in triploid brown trout Salmo trutta were all comparable with established information for diploid rainbow trout Oncorhynchus mykiss . Therefore, it was concluded that triploidy is not associated with a major deficiency in maximum cardiac performance. However, a heightened sensitivity to ryanodine was discovered, which indicated an enhanced role for the sarcoplasmic reticulum in excitation‐contraction coupling in these triploid fish. It is suspected that the enhanced role of the ryanodine receptor may be a cellular compensation related to larger cardiac myocytes. It was also clearly established that there was a plateau in maximum cardiac performance between 14 and 18° C and this plateau might be a contributing factor to the reduced factorial aerobic scope and increased fish mortality observed at 18° C.

Cardiorespiratory status of triploid brown trout during swimming at two acclimation temperatures - J. Altimiras; M. Axelsoon; G. Claireaux; C. Lefrançois; C. Mercier; A. P. Farrell (Journal of Fish Biology, 2002)
At 14° C, standard metabolic rate (75·1 mg O 2 h −1 kg −1 ), routine metabolic rate (108.8 mg O 2 h −1 kg −1 ), active metabolic rate ( c . 380 mg O 2 h −1 kg −1 ), critical swimming speed (U crit 1·7 BL s −1 ), heart rate 47 min −1 ), dorsal aortic pressure (3·2 kPa) and ventilation frequency (63 min −1 ) for triploid brown trout Salmo trutta were within the ranges reported for diploid brown trout and other salmonids at the same temperature. During prolonged swimming ( c . 80% U crit ), cardiac output increased by 2·3‐fold due to increases in heart rate (1·8‐fold) and stroke volume (1·2‐fold). At 18° C, although standard and routine metabolic rates, as well as resting heart rate and ventilation frequency increased significantly, active metabolic rate and certain cardiorespiratory variables during exercise did not differ from those values for fish acclimated to 14° C. As a result, factorial metabolic scope was reduced (2·93‐fold at 18° C v . 5·13‐fold at 14° C). Therefore, it is concluded that cardiorespiratory performance in triploid brown trout was not unusual at 18° C, but that reduced factorial metabolic scope may be a contributing factor to the mortality observed in triploid brown trout at temperatures near 18° C.

Comparison of results from several AOGCMs for global and regional sea-level change 1900-2100 - J. M. Gregory; J. A. Church; G. J. Boer; K. W. Dixon; G. M. Flato; D. R. Jackett; J. A. Lowe; S. P. O'Farrell; E. Roeckner; G. L. Russell; R. J. Stouffer; M. Winton (Climate Dynamics, 2001)

Sulfur K-edge XANES study of local electronic structure in ternary monosulfide solid solution [(Fe, Co, Ni) 0.923 S] - S. P. Farrell; M. E. Fleet (Physics and Chemistry of Minerals, 2001)

National Survey of Hepatitis Testing and Vaccination Services Provided by Drug Services in England and Wales - A. J. Winstock; J. Sheridan; S. Lovell; M. Farrell; J. Strang (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Gastrointestinal blood flow in the red Irish lord, Hemilepidotus hemilepidotus : long-term effects of feeding and adrenergic control - M. Axelsson; H. Thorarensen; A. P. (Tony) Farrell; S. Nilsson (Journal of Comparative Physiology B, 2000)

Bovine mammary explant versus primary cell cultures: Effect of bovine somatotropin and insulinlike growth factor-I on DNA content and protein synthesis - J. E. Keys; E. Cifrian; A. J. Guidry; H. M. Farrell (In Vitro Cellular & Developmental Biology - Animal, 1997)

Molecular and biological characterization of new strains of murine cytomegalovirus isolated from wild mice - T. W. M. Booth; A. A. Scalzo; C. Carrello; P. A. Lyons; Helen E. Farrell; G. R. Singleton; G. R. Shellam (Archives of Virology, 1993)

Resonance mode analysis for volume estimation of asymmetric branching structures - David T. Raphael; M. A. Farrell Epstein (Annals of Biomedical Engineering, 1989)